A Person-Centered Examination of Motivational Profiles and Employment Preferences Across Age Groups - Wang, Daisy; Wang, Zheni (Academy of Management Proceedings, 2026)
This cross-sectional study examines how age-group differences in work motivation and basic psychological needs relate to preferences between self- and wage-employment. Drawing on Self-Determination and Lifespan Development Theories, age groups are conceptualized as life-stage categories rather than birth cohorts, and motivational profiles are compared in the post-COVID US labor market. Online survey data were collected from 1,484 adult Americans across five age groups, from Gen Z to Traditionalist. Multi-group CFA for measurement invariance, ANOVA, latent mean comparisons, and latent profile analysis with distal outcome comparisons were performed. Results indicated significant, albeit small, age-group differences in employment preferences and motivational constructs. Gen Z-young adults reported relatively stronger preference for self-employment than older age-groups, whereas Gen Y (Millennials), early to mid-career, exhibited the highest autonomous motivation, the lowest amotivation, and greater satisfaction of autonomy and competence needs at work. Five distinct motivational profiles were identified from latent profile analyses; low-intensity and controlled–amotivated profiles were most strongly associated with a preference for self-employment, whereas a high-involvement yet conflicted profile showed the strongest preference for wage-employment. Younger participants, particularly Gen Z and Gen Y, were more likely to fall into globally elevated and psychologically complex profiles. Overall, the findings suggest that age-linked life stages are associated with nuanced motivational configurations that only modestly translate into employment preferences, highlighting the value of developmentally sensitive, person-centered approaches to understanding contemporary work, employment preferences, and entrepreneurial orientations.
Keywords: AOM Annual Meeting Proceedings 2026; AOM Philadelphia 2026; Human Resources; Paper - Abstract Only; dept.mgt

The Conditional Value of Consumer Satisfaction: Innovation Choice Under Economic Recession - Yoo, Jae Kyun; Lee, Minjae (Academy of Management Proceedings, 2026)
Economic recessions reshape consumer expectations and amplify scrutiny, altering how firms’ capabilities translate into performance. This study examines how recession-driven shifts in consumer expectations intensify the vulnerability of firms with high preexisting consumer satisfaction and how their innovation choices shape the extent to which this capability becomes a liability. We argue that recessions heighten negative reactions to perceived performance deviations, making high pre-recession satisfaction—typically a strategic strength—especially vulnerable. Using data from the U.S. automobile industry spanning the 2008 financial crisis, we find that consumer satisfaction declines significantly during recession and that firms with higher preexisting satisfaction experience disproportionately larger losses. We further demonstrate that innovation strategy plays a decisive moderating role: incremental product redesigns, which preserve familiarity and signal stability, mitigate the recession penalty for high-satisfaction firms, whereas new product introductions do not offer comparable protection. The study provides a theoretical account of how economic downturns can invert the value of demand-side capabilities and identifies conditions under which incremental innovation outperforms more transformative approaches. Managerially, the findings offer guidance on how firms can align innovation portfolios with shifting consumer psychology to protect reputational assets and sustain performance during an economic disruption.
Keywords: AOM Annual Meeting Proceedings 2026; AOM Philadelphia 2026; Paper - Abstract Only; Technology and Innovation Management; dept.mgt

The future is here! Recognizing the need to revitalize and transform business education via digital integration - Philip, Jestine; Schmidt, Gordon B.; Simha, Aditya; Rosen, David (Business Horizons, 2026)
Business education is undergoing rapid transformations thanks to advancements in emerging technologies. Business school leaders are engaging in identifying approaches to revitalize business education, preparing students to succeed in a technologically advancing workplace. Primarily anchored in the concept of digital transformation, our article provides practical guidance to help business schools integrate artificial intelligence (AI) into their curricula and infrastructure, benefiting students, faculty, administration, and leadership. We offer a roadmap that lays out current industry trends and articulates pertinent action items, related cost efforts, and associated benefits for business education. This article positions business schools to instill a human-AI augmentation mindset in students, faculty, staff, and leadership that prepares them to work with ever-changing technologies. Regularly revising business course curricula to stay aligned with evolving industry needs is key to providing topical content and meaningful skill development opportunities for students. We argue that these efforts directly enhance student employability and learning, better preparing students to succeed in the increasingly technology-enabled workplace. © 2026 Kelley School of Business, Indiana University. Published by Elsevier Inc. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Artificial intelligence (AI); Business schools; Digital transformation; Generative AI (GenAI); Human-AI augmentation mindset; dept.mgt

From fragmentation to integration: finding the psychological and instrumental common ground for algorithmic management and marketing - Wang, Zheni; Wang, Emma; Zhu, Guorong (SSRN Electronic Journal, 2026)
Keywords: Common ground; Corporate governance; Fragmentation (computing); Service (business); Spillover effect; Stakeholder; Stakeholder analysis; Stakeholder theory; dept.mgt; dept.mrk

Vacillation and performance: how alignment with environmental changes drives effective vacillation - Lee, MinJae (Academy of Management Proceedings, 2025)
Keywords: Empirical research; Environmental effect; Mechanism (biology); Period (music); dept.mgt

Developing entrepreneurship competence in STEM graduate students through a fellowship model - Wang, Zheni; Daneshmandi, Leila; Christodoulidou, Andri (Academy of Management Proceedings, 2025)
Keywords: Cognition; Competence (human resources); Entrepreneurship; Entrepreneurship education; Graduate students; Higher education; Mindset; Qualitative research; Value (mathematics); dept.mgt

Building positive experiences for sustainable development - Wang, Zheni; Zhu, Guorong; Zhang, Mengyi; Wang, Emma; Lv, Shuangning; Zheng, Jiawei; Shen, Yan; Steckler, Erica (Academy of Management Proceedings, 2025)
Keywords: Creativity; Face (sociological concept); Grounded theory; Stakeholder; Stakeholder engagement; Sustainability; Sustainable development; Work (physics); dept.mgt; dept.mrk

Museum experiences as innovative pedagogy in contemplative management education for sustainability - Yang, Charlie; Ivanova, Ekaterina; Ivanova, María (Academy of Management Proceedings, 2025)
Keywords: Contemplation; Curriculum; Environmental education; Experiential learning; Mindset; Reflective practice; Sustainability; Sustainable business; Visual arts education; dept.mgt

The relationship between quality management and innovativeness: an empirical study - Triana-Garcia, Randy; Muthuraj, Birasnav; Rincón-Guio, Cristian (6th South American Conference on Industrial Engineering and Operations Management, 2025)
This study aims to explore the relationship between four key elements of quality management: teamwork, feedback, motivational barriers, and need analysis, and their contribution to improve innovativeness in the Colombian educational context. Drawing on the concepts of control and learning in the quality management theory and using publicly available responses collected from the Colombian teachers who participated in the TALIS 2018 survey, this research study examines how teachers perceive these elements within their institutions and their potential impact on fostering innovativeness among teachers. The study adopts an empirical approach to analyze these relationships, employing a descriptive and inferential statistical framework to uncover patterns and correlations. By focusing on the school practices in Colombia, the research seeks to provide insights into how quality management practices can drive innovation in educational settings. Findings identify specific patterns in the implementation of these practices and their relationship with innovativeness among teachers, offering actionable recommendations for improving teaching strategies in education to improve quality. This study contributes to the broader understanding of management’s role in teaching and learning, offering valuable implications for policymakers and practitioners in developing countries. The novelty of this work lies in its analyses of TALIS data to assess quality management practices and their direct influence on fostering innovation.
Keywords: Business; Computer science; Empirical research; Knowledge management; Mathematics; Process management; Quality (philosophy); Statistics; dept.mgt

Bridging indigenous art and sustainability: transformative museum learning in management education - Yang, Charlie (Humanistic Management Journal, 2025)
Keywords: Bridging (networking); Computer science; Ecology; Environmental ethics; Indigenous; Pedagogy; Philosophy; Sociology; Sustainability; Transformative learning; dept.mgt

How Do Firms Build Green Supply Chain Learning System? A Theoretical Framework and Directions - Birasnav, M.; Han, Seungmin; Arora, Ridhi; Sangar, Ruby (Corporate Social Responsibility and Environmental Management, 2026)
Keywords: Green innovation; Mechanism (biology); Perspective (graphical); Resource (disambiguation); Supply chain; Supply chain management; Workforce; corporate social responsibility; dept.mgt; environmental performance; exploitation; exploration; green supply chain; leadership; learning system

Framing the future: how museums shape sustainability mindsets in business education - Yang, Charlie; Ivanova, Ekaterina; Ivanova, Maria (The Power of Arts-Based Pedagogies: Transforming Mindsets to Shape Our Future, 2026)
Recent research proposes that arts-integrated teaching approaches in business education can nurture students' aesthetic sensitivity and emotional capacities, such as self-awareness and empathy. In this chapter, we examine the pedagogical possibility of art appreciation in art museums as a consciousness-raising practice, especially for the sake of cultivating business students' environmental awareness in two different contexts. We have analyzed American and Russian students' reflective essays based on their museum visits in order to explore how business students make sense of their aesthetic experiences and how art appreciation helps them to develop their sustainability mindset in a creative learning space. Through attentive viewing of the works of art, students have learned some key insights from their aesthetic appreciation at art museums. These insights not only facilitated honing their emotional skills, but also deepened their environmental awareness and heightened their sense of personal empowerment to act upon these newly acquired insights and values ensuing from art appreciation. After identifying six key themes extracted from both groups of students' essays based on their museum learning, we further discuss the pedagogical implications of contemplative art appreciation in museums as a means of contributing to more innovative and sustainable management education. © 2026 selection and editorial matter, Ekaterina Ivanova, Isabel Rimanoczy and Divya Singhal; individual chapters, the contributors.
Keywords: dept.mgt

Quality management and safety performance: the influence of ethical leaders among public sector employees - Birasnav, M.; Dahiya, Rinki; Dalpati, Avadhesh (The TQM Journal, 2026)
Keywords: Ethical leadership; Incentive; Job satisfaction; Motivation for QM implementation; Perceived safety performance; Public sector; Quality (philosophy); Structural equation modeling; Survey data collection; Test (biology); Work (physics); dept.mgt

Rethinking Motivation and Reward Management: What We Know and Do not Know - Wang, Zheni (Edward Elgar Publishing Ltd., 2025)
This innovative book examines the controversial relationship between motivation and rewards from multiple theoretical and practical perspectives. It analyzes cutting-edge research on work motivation and reward management's economic and psychological roots and identifies future directions for advancement in the field. © Zheni Wang 2025.
Keywords: Compensation And Benefits; Motivation At Work; Reward Management; Self-Regulations; Total Rewards; Work Engagement; dept.mgt

Understand the Changes in Motivation at Work: Empirical Studies Using Self-Determination Theory-Based Interventions - Wang, Zheni; Briand, Mélanie (Behavioral Sciences, 2025)
Managers often need to stay motivated and effectively motivate others. Therefore, they should rely on evidence-based interventions to effectively motivate and self-motivate. This research investigated how self-determination theory-based interventions affect employees' motivation dynamics and motivational consequences within short time frames (i.e., within an hour, within a few weeks or months) in two empirical studies. Study one focused on assessing the effectiveness of a one-day training workshop in helping to improve managers' work motivation, basic psychological needs satisfaction/frustration, subordinates' motivation, and perceptions of managers' needs-supportive/thwarting behaviors within a few weeks. Results support the effectiveness of the training, as managers were rated by their direct subordinates as having fewer needs-thwarting behaviors and reported self-improvement in needs satisfaction and frustration six weeks after completing the training program. Study two used the mean and covariance structure analysis and tested the impact of three types of basic psychological needs-supportive/thwarting and control conditions (3 × 2 × 1 factorial design) on participants' situational motivation, vitality, and general self-efficacy for playing online word games within 30 min. Multi-group confirmatory factor analysis (CFA) confirmed the scalar measurement invariance, then latent group mean comparison results show consistently lower controlled motivation across the experimental conditions. During a quick online working scenario, the theory-based momentary intervention effectively changed situational extrinsic self-regulation in participants. Supplementary structural equation modeling (SEM; cross-sectional) analyses using experience samples supported the indirect dual-path model from basic needs satisfaction to vitality and general efficacy via situational motivation. We discussed the theoretical implications of the temporal properties of work motivation, the practical implications for employee training, and the limitations.
Keywords: Applied psychology; Autonomy; Computer science; Confirmatory factor analysis; Psychological intervention; Psychology; Self-determination theory; Situational ethics; Social psychology; Structural equation modeling; Work (physics); Work motivation; dept.mgt; employee training and development; motivation change; self-determination theory; theory-based interventions

Gender congruence and entrepreneurial investments: the role of others’ reactions - Wieland, Alice (International Journal of Gender and Entrepreneurship, 2025)
The purpose of this research is to explore the decision processes that underlie the gender gap in entrepreneurial investments. The present research explores how gender congruence with a sex-typed business opportunity influences anticipated reactions from others who may provide or withhold support and resources, how these affect the assessed probability of venture success and the amount the entrepreneur is willing to invest (WTI) in the opportunity.,A theoretical model is presented and empirically tested via path analysis. A pilot and an experimental study model explore how gender congruence influences entrepreneurial investment decisions. The experimental study uses a repeated measures design examining the experimental effects two sex-typed business opportunities crossed with participant gender (gender congruence) on anticipated others’ reactions, assessed probability of venture success and investment amount (WTI).,Gender congruence of a business opportunity influences anticipated others’ reactions, whether they will be supportive or not, of pursuing the opportunity. This in turn influences the estimated probability of success of the venture and the amount the prospective entrepreneur is willing to invest in it. These socio-cognitive decision processes reinforce the gender gap in entrepreneurship since participants anticipate less access to others’ support for gender incongruent opportunities. Although the mediational model indicates most proposed relationships and paths are invariant across genders, the exception was that women did not report higher WTI for the gender congruent venture.,The research applies the latest thinking in social psychology on gender norm violations to entrepreneurship, measuring how anticipated reactions from others are a factor in predicting estimates of venture success probability and self-investments.
Keywords: dept.mgt; peer-reviewed

Gendered cognitions: a socio-cognitive model of how gender affects entrepreneurial preferences - Wieland, Alice M., Markus, Kemmelmeier, Vishal K., Gupta; McKelvey, William (Entrepreneurship & Regional Development, 2019)
This research explores the social-cognitive factors which lead both women and men to pursue ventures consistent with their gendered social identity, therefore, reinforcing the gender gap in entrepreneurship. We measured the self-assessments of individuals presented with experimentally manipulated entrepreneurial opportunities that were either consistent or inconsistent with their self-reported gender. A theoretical model derived from Social Role Theory is presented and tested. It posits that a gender match (mismatch) with the entrepreneurial opportunity results in higher (lower) reported self-efficacy, anticipated social resources, and venture desirability and lower (higher) venture risk perceptions. The experimental data are tested in a sequential mediation SEM model. We find evidence that self-efficacy and anticipated social resources mediate the effect of gender congruency on perceived risk and venture desirability. The results provide insight into the insidious barriers that play a role in reproducing a gender gap in entrepreneurial outcomes by ‘nudging’ women into lower-return ventures in less lucrative industries.
_eprint: https://doi.org/10.1080/08985626.2018.1551787
Keywords: Entrepreneur; gender; gender gap; gender norms; gender role; opportunity evaluation; sex

The Impact of Attentiveness Interventions on Survey Data - Fuller, Christie; Simmering, Marcia; Waterwall, Brian; Ragland, Elizabeth; Twitchell, Douglas; Wall, Alison (Educational and Psychological Measurement, 2025)
Social and behavioral science researchers who use survey data are vigilant about data quality, with an increasing emphasis on avoiding common method variance (CMV) and insufficient effort responding (IER). Each of these errors can inflate and deflate substantive relationships, and there are both a priori and post hoc means to address them. Yet, little research has investigated how both IER and CMV are affected with the use of these different procedural or statistical techniques used to address them. More specifically, if interventions to reduce IER are used, does this affect CMV in data? In an experiment conducted both in and out of the laboratory, we investigate the impact of attentiveness interventions, such as a Factual Manipulation Check (FMC) on both IER and CMV in same-source survey data. In addition to typical IER measures, we also track whether respondents play the instructional video and their mouse movement. The results show that while interventions have some impact on the level of participant attentiveness, these interventions do not appear to lead to differing levels of CMV.
Keywords: Affect (linguistics); Applied psychology; Communication; Mathematics; Medicine; Post hoc; Psychological intervention; Psychology; Quality (philosophy); Social psychology; Statistics; Survey data collection; Survey research; dept.mgt; peer-reviewed

Bridging employees’ perceptions of corporate social responsibility, sense-making for meaningfulness, and work engagement for successful self-regulation - Wang, Z.; Carroll, S.; Wang, E.H. (Behavioral Sciences, 2024)
In response to calls for research on the psychological mechanisms, such as perceptions and attitudes toward corporate citizenship, in promoting positive outcomes at work, this research presents a novel approach by empirically testing a calling conditioned path model from P perception of corporate CSR (P-CSR) to work engagement via meaningfulness under the theoretical framework of self-determination theory. Survey data collected from 224 corporate employees in the US were tested using the PROCESS plugin (version 4.3) in SPSS. The regression results supported the positive direct and indirect paths from employees’ P-CSR to meaningfulness and work engagement but not the conditioning effect of calling work orientation. This study’s unique findings, limitations, future research, and implications are discussed, expanding micro-CSR research and unboxing the management assumptions of employees as purposeful autonomous agents seeking consistent interpretations and authentic perceptions of organizational CSR activities during their sense-making processes. Non-confirming of the calling conditioning the path model shed light on it being a dynamic multi-dimensional and multi-level construct to be further researched. © 2024 by the authors.
Keywords: calling work orientation; dept.mgt; micro-CSR; peer-reviewed; work engagement

A metacognitive approach to understanding what marker variables measure - Leonard, Stephanie; Simmering, Marcia J.; Wall, Alison E. (Current Psychology, 2024)
Marker variables provide an efficacious means of post hoc detection of common method variance (CMV) in data. These variables are measured in the same way as substantive variables, but because they are conceptually unrelated to the variables of interest, they are believed to be a proxy for CMV. Although marker variables have demonstrated effectiveness, questions remain as to what they actually measure, and thus, why they work. This lack of knowledge prevents researchers from choosing appropriate marker variables to include in same source surveys. The purpose of this research is to determine how four different marker variables account for common rater effects which can cause CMV. A metacognitive approach is used to develop an empirical study using two samples, with a focus on the specific rater effects of mood state, transient mood, consistency motif, and illusory correlations. Findings indicate that these marker variables elicit similar respondent reactions and do not create a notable psychological separation between substantive variables. Additionally, there is evidence that respondents’ use of consistency motifs and illusory correlations influence substantive variable relations. Finally, using the confirmatory factor analysis marker technique, data from two samples indicate the presence of CMV, but not bias from CMV, indicating that the problem of artificially inflated results due to CMV may be overstated.
Keywords: Common method variance; Marker variables; Metacognition; Survey research; dept.mgt; peer-reviewed

The Green Energy Sector - Nodoushani, Omid; Van den Abbeele, Isaline; Stewart, Carol (Competition Forum, 2015)
Thinking "Green" has become a significant economic trend lately. This research paper offers a better understanding of the background facts of the current hype surrounding "Green Energy." First, the problem of global warming is investigated. Europe has taken a lead role in the fight against global warming in order to meet their objective of 20% renewable energy production by 2020. Many possibilities exist to transform raw biomass into bioenergy fuels, which can then be used for specific energy production purposes: electricity production, warming or transport. Biodiesel, bioethanol, biogas and many other fuels can be produced from biomass.
Num Pages: 6 Place: Indiana, United States
Keywords: Alternative energy; Alternative energy sources; Biomass; Carbon dioxide; Chlorofluorocarbons; Climate change; Energy industry; Environmental impact; Global warming; Greenhouse effect; Greenhouse gases; Nobel prizes; Renewable resources; Studies; Temperature; Trends; dept.mgt

Recycling and Its Effects on the Environment - Nodoushani, Omid; Stewart, Carol; Kaur, Manpreet (Competition Forum, 2016)
Consumers and businesses have an ethical obligation to do their part to reuse or recycle unwanted items. However, while some consumers and businesses do reuse or recycle e-waste, glass, metal, plastic, paper or textiles, more could be done. Even with environmentalists warning of potential chemical hazards these items produce in landfills, an estimated 85 percent of landfills are filled with unwanted waste. The recycling industry along with local government run media campaigns to raise awareness; however, as a result consumers and businesses may be experiencing information overload which may have a negative impact on consumers ' recycling efforts.
Num Pages: 5 Place: Indiana, United States
Keywords: Communication; Consumers; Consumption; Electronic waste; Electronics; Energy consumption; Environmental impact; Environmental protection; Environmentalists; Greenhouse gases; Information overload; Landfill; Natural resources; Plastics; Raw materials; Recycling; Textiles; dept.mgt

The interplay of power, incentives, academic freedom, and gender equity - Wieland, Alice; Jansen, Amy (Journal of Academic Freedom, 2024)
Alice Wieland and Amy Jansen explore the intersection of how power, adverse incentives, and gender bias combine to perpetuate gender inequity in higher education.
Keywords: dept.lib; dept.mgt

Do schools have hindrance of quality to promote innovativeness? Examining the role of empowering leadership and stakeholder involvement - Birasnav, M.; Dahiya, Rinki; Bharti, Teena (International Journal of Quality & Reliability Management, 2024)
Purpose Schools provide high priorities to offer innovative curricular and cocurricular programs, and leaders make necessary efforts to promote enablers and overcome disablers for sustaining their innovativeness. With the background of quality management and stakeholder theories, the present study examines the interplay of hindrances to quality between empowering leadership, stakeholder involvement and organizational innovativeness. Design/methodology/approach Responses of 157 American school principals collected through the Teaching and Learning International Survey 2018 by the Organization for Economic Cooperation and Development were used and analyzed to test the proposed hypotheses. Findings Results show that empowering leadership behaviors of school principals support promoting organizational innovativeness, and involvement of stakeholders with the school activities also promotes organizational innovativeness. Interestingly, when American schools faced a high level of hindrance to providing quality education to their students, principals’ high level of empowering leadership behaviors promoted organizational innovativeness. Originality/value This is the first time in the literature that the interplay between empowering leadership, stakeholder involvement and hindrance of quality education has been examined to promote organizational innovativeness.
Keywords: Empowering leadership; Hindrance of quality education; Organizational innovativeness; Quality management; Stakeholder involvement; dept.mgt; peer-reviewed

Unboxing the temporal patterns of employee engagement: a daily and weekly analysis of needs satisfaction, work motivation and employee well-being - Wang, Z. (Evidence-based HRM, 2024)
Purpose: This research used a temporal approach to operationalize employee engagement, capturing subjective/objective time of the day and day of the week to analyze the dynamic patterns of employees’ daily/weekly well-being, basic needs satisfaction, and situational work motivation under the integrated framework of self-determination theory. Design/methodology/approach: Multi-level data was collected using the survey structure outlined under the day reconstruction methodology (DRM) with samples of Canadian part-time working undergraduate students and full-time US corporate employees (1980 work episodes reported by 321 participants). Findings: Multi-level confirmatory factorial analysis results supported the measurement invariance for within-person variables in all the working episodes across the US and Canada samples. Structural equation modeling path analysis results, using the within-person variables, captured the daily temporal patterns that employees’ well-being (vitality and positive affect), basic psychological needs (autonomy and relatedness), and situational autonomous motivation started at a high level and decreased with both subjective and objective time of the day. Negative affect showed asymmetric daily and weekly temporal patterns compared to positive affect. A few indirect paths were found, including one from the subjective time of the day to employee well-being (vitality and affect) via situational autonomous motivation and another one from the day of the week to vitality and positive affect via relatedness needs satisfaction and situational autonomous motivation. Research limitations/implications: The socio-cultural and business impacts of work scheduling practices and implications for theory-driven, evidence-based organizational development practices were discussed together with the research limitations. Practical implications: Results on how the variations in self-regulation during the performance of different work tasks in a single work event help practitioners to connect repeated situational motivational change patterns to effective supervision. HR business partner can also utilize such findings to shape evidence-based practice to improve employee engagement. Originality/value: This research is one of the few pioneer studies to look into how temporal factors, such as work scheduling, affect employees' well-being through the dynamic understanding of the mediated path model from time to employee well-being via psychological engagement conditions such as motivation and needs satisfaction. © 2024, Emerald Publishing Limited.
Keywords: Self-regulation; Temporal analysis; Work scheduling; dept.mgt; peer-reviewed

Factor Structure of Organizational Commitment: Differences between U.S. and South Korean Samples - Lee, Jo Ann; Yang, Chulguen (Psychological Reports, 2005)
The current study compared the factor structures of the construct of organizational commitment between two samples of financial employees, one from the U.S. ( n = 103) and one from South Korea ( n = 109). Participants completed a 26-item questionnaire. Two factors (an affective component and a normative component) emerged for the U.S. sample; only one factor for the Koreans. Results suggest that culture should be considered when trying to assess organizational commitment.
Keywords: dept.mgt; peer-reviewed

A cross‐national analysis of affirmative action: an evolutionary psychological perspective - Yang, Chulguen; D'Souza, Geeta C.; Bapat, Ashwini S.; Colarelli, Stephen M. (Managerial and Decision Economics, 2006)
Abstract Affirmative action (AA) is a government policy permitting employers and universities to give preferential treatment to applicants from specific (e.g. racial) groups. We present a comparative analysis of AA in six countries (India, USA, Malaysia, Canada, South Africa, and Brazil) and explain similarities among these programs according to universal psychological mechanisms and variation according to cultural–historical contexts. It appears that similarities in contextual conditions (e.g. democratic government, multi‐ethnic states) interact with ancient psychological mechanisms (e.g. fairness, cheater detection, alliance tracking) to provide at least part of the motivation for the development and expansion of AA, despite its problematic consequences. Copyright © 2006 John Wiley & Sons, Ltd.
Keywords: dept.mgt; peer-reviewed

Understanding Adaptive Functions of Kinship in Immigrant Entrepreneurship: An Evolutionary Perspective - Yang, Chulguen; Colarelli, Stephen M.; Han, Kyunghee (Usiness Research Yearbook, 2008)
Keywords: dept.mgt; peer-reviewed

Immigrant Entrepreneurship from a Neo-Darwinian Co-Evolutionary Perspective - Yang, Chulguen; Colarelli, Stephen M.; Han, Kyunghee (Journal of Business Management & Change, 2008)
Keywords: dept.mgt; peer-reviewed

Asian Entrepreneurs Going Green: Cases of China and Korea - Goralski, Margaret A.; Yang, Chulguen (Usiness Research Yearbook, 2008)
Keywords: dept.mgt; peer-reviewed

Darwin’s Deadly Legacy? Why Evolution Matters for Management Studies - Yang, Chulguen; Colarelli, Stephen M.; Holston, Kayong (Research Yearbook, 2010)
Keywords: dept.mgt; peer-reviewed

Understanding human nature: From an evolutionary psychological perspective - Yang, C.; Colarelli, S.; Holston, K. (Journal of International Business Disciplines, 2011)
Keywords: dept.mgt; peer-reviewed

The E-Print Industry and Bookseller Market: A Strategic Perspective - Nodoushani, Omid; Yang, Chalie (Competition Forum, 2011)
Keywords: dept.mgt; peer-reviewed

A Comparative Study on Native-Born and Foreign-Born Female Entrepreneurs: A Narrative Approach - Yang, Chulguen Charlie; Goralski, Margaret A. (Business Research Yearbook, Goralski, Margaret A, 2011)
Keywords: dept.mgt; peer-reviewed

The creative use of music in teaching organizational behavior - Yang, Chulguen (Usiness Research Yearbook, XVIII, 2011)
Keywords: dept.mgt; peer-reviewed

A Creative Use of Films to Enhance Emotional Awareness and Cultural Intelligence - Yang, Chulguen Charlie; Nodoushani, Omid (Research Yearbook, 2012)
Keywords: dept.mgt; peer-reviewed

Kin Altruism, Psychological Contract and Commitment in Immigrant Businesses: Some Theoretical Propositions - Yang, Chulguen Charlie (QRBD, 2014)
Keywords: dept.mgt; peer-reviewed

Mindfulness and Its Pedagogical Application in Business Education - Chulguen (Charlie) Yang; Goralski, Margaret A. (Journal of International Business Disciplines, 2016)
Mindfulness has gained significant attention and momentum in business and popular culture in the US, Europe, and Australia. There is, however, a paucity of literature on how business students make sense of mindfulness and its practices. Based on our experiences of adopting mindfulness and mindfulness meditation in our teachings of management courses, we have explored how business students make sense of mindfulness and meditation. From a phenomenological perspective, we have examined our students' meditation journals, essays, and their own research on the topic of mindfulness. Based on the findings of previous empirical studies on the positive effects of mindfulness practices and our reflections on the pedagogical potential of mindfulness meditation for business education, we have emphasized that the practice of presence through mindfulness tends to enhance the business students' self-awareness and emotional skills. The implications of adopting mindfulness research and brief and deliberate practices into the business curriculum to develop embodied wisdom are also discussed.
Keywords: BUSINESS education; BUSINESS students; MANAGEMENT; MEDITATION; MINDFULNESS; POPULAR culture; UNITED States; dept.mgt; peer-reviewed

Domain specificity of sex differences in competition - Wieland, Alice; Sarin, Rakesh (Journal of Economic Behavior & Organization, 2012)
There has been much recent literature about sex differences in competition, mostly noting that women are innately less competitive than men (Croson and Gneezy, 2009). This article examines the hypothesis that sex differences in propensity to compete are domain specific. We conducted a 2 (sex)×4 (domain) experiment with 434 participants examining competition decisions, familiarity with the domain, and performance. We find no overall sex differences in rates of competition when collapsing across all four domains, but do find sex differences in rates of competition for individual domains. Additionally we examined the importance of winning at competition on self-esteem using the Contingencies of Self-Worth, Competition subscale (Crocker et al., 2003) and find that the subscale fully mediates the effect of sex on the strength of competitive pay preferences.
Keywords: Competition; Decision-making; Gender differences; Risk; Sex differences; dept.mgt

Gender differences in the endowment effect: Women pay less, but won’t accept less - Wieland, Alice; Sundali, James; Kemmelmeier, Markus; Sarin, Rakesh (Judgment and Decision Making, 2014)
We explore different contexts and mechanisms that might promote or alleviate the gender effect in risk aversion. Our main result is that we do not find gender differences in risk aversion when the choice is framed as a willingness-to-accept (WTA) task. When the choice is framed as a willingness-to-pay (WTP) task, men are willing to pay more and thus exhibit lower risk aversion. However, when the choice is framed as a willingness to accept task, women will not accept less than men. These findings imply gender differences in the endowment effect. We also find that the effect size of the gender difference in risk aversion is reduced or eliminated as the context changes from tasks framed as gambles to other domains; and that attitudes toward gambling mediate the gender effect in gambling framed tasks.
Keywords: dept.mgt; endowment effect; gambling attitudes; gender; peer-reviewed; risk attitudes; risk aversion; sex differences

Boosting Performance on an Evaluative Math Test: Goal Activation vs Self-Affirmation - Wieland, Alice M.; Burnham, Thomas A. (Psychological Reports, 2016)
This study compared the effectiveness of goal activation versus self-affirmation and a control condition as interventions for increasing performance on an evaluative task (a difficult math test; N = 78; M age = 20.3 yr., SD = 1.9). Although there has been much recent literature on the effects of activating goals, the existing literature does not examine possible spillover effects of activating goals on performance tasks. Results indicated that goal activation resulted in significant performance enhancements over both the self-affirmation and control conditions, while self-affirmation did not improve performance significantly relative to the control condition. Additionally, interest in the task, as a cue for self-regulatory resources, mediated the effect of goal activation on increased performance.
Keywords: dept.mgt

Risk aversion for decisions under uncertainty: Are there gender differences? - Sarin, Rakesh; Wieland, Alice (Journal of Behavioral and Experimental Economics, 2016)
It has become well accepted that women are more risk averse than men. For objective probability gambles, typically used in eliciting risk aversion, we find women generally have a lower valuation than men, thus exhibiting greater risk aversion. This paper investigates whether this finding extends to decisions under uncertainty – where probabilities are not given and individuals may assign different probabilities to the same event (e.g. outcomes of award shows or sporting events).We find that for decisions under uncertainty, men and women value the bets similarly, both before and after controlling for participants' subjective probabilities.
Keywords: Decision-making; Gender; Risk aversion; Subjective probability; Uncertainty; dept.mgt; peer-reviewed

Antecedents of corporate entrepreneurship in Iran: the role of strategic orientation and opportunity recognition - Kakapour, Saba; Morgan, Todd; Parsinejad, Salman; Wieland, Alice (Journal of Small Business & Entrepreneurship, 2016)
In a study of 130 Iranian small- and medium-sized enterprises (SMEs), we predict and find that market orientation, learning orientation, and their interaction are positively related to opportunity recognition, which impacts firm-level corporate entrepreneurship positively. This study makes two important contributions to the corporate entrepreneurship literature. First, the majority of studies on corporate entrepreneurship concern western economies or China; as such, we broaden research on the international context of corporate entrepreneurship by examining a unique dataset of Iranian SMEs, which have grown significantly in recent years during their transition to knowledge-based enterprises. Second, we build upon previous literature on corporate entrepreneurship antecedents by explicating and testing the relationships of how and when learning orientation and market orientation affect opportunity recognition and the development of corporate entrepreneurship.
_eprint: https://doi.org/10.1080/08276331.2016.1168676
Keywords: Apprentissage organisationnel; Entreprenariat d'entreprise; Entreprises fondées sur les connaissances; Iran; Orientation de marché; Orientation sur l'apprentissage; Petites et Moyennes Entreprises; Repérage des débouchés; corporate entrepreneurship; dept.mgt; knowledge-based enterprises; learning orientation; market orientation; opportunity recognition; organizational learning; peer-reviewed; small and medium-sized enterprises

Designing Entrepreneurship Experiments: A Review, Typology, and Research Agenda - Hsu, Dan K.; Simmons, Sharon A.; Wieland, Alice M. (Organizational Research Methods, 2017)
This article discusses the current and potential application of experimental methods to the study of entrepreneurship phenomena. Drawing on a review of experimental studies in entrepreneurship research, we discuss the advantages and disadvantages of experimental research designs for entrepreneurship research as a primer for those interested but not overly familiar with these methods. To advance research agendas and theory in the field, we introduce a typology of experimental manipulations that highlight alternative design choices based on the nature of their participant impact and realism of context. Finally, we provide an overview of areas of opportunity within the entrepreneurship literature for application of methods best suited to provide greater insight into the causal mechanisms at play.
Keywords: dept.mgt; peer-reviewed

Culture, benevolent and hostile sexism, and entrepreneurial intentions - Stedham, Yvonne; Wieland, Alice (International Journal of Entrepreneurial Behavior & Research, 2017)
Purpose In this study, the authors relate cultural masculinity to individual level sexist beliefs (hostile and benevolent sexism) and gendered entrepreneurial stereotypes. The purpose of this paper is to explore whether hostile and benevolent sexism affect entrepreneurial intentions and whether this relationship is mediated by gendered entrepreneurial stereotypes. Design/methodology/approach The proposed relationships are explored using a sample of 192 participants from the USA and India with varying interest in starting a business. An online survey instrument was used to collect the data. Regression and mediation analyses were used to analyze the data. Findings The authors find that both hostile and benevolent sexism are positively related to entrepreneurial intentions of both men and women. However, only benevolent sexism is related to both the masculine and feminine gender traits ascribed to entrepreneurs. Interestingly, the authors find support that hostile sexism is actually positively related to feminine traits ascribed to entrepreneurs, albeit with a small effect size. The authors do not find any support that these results vary by participant gender; the findings are implicated for both men and women alike. The authors find that for both hostile and benevolent sexism only the feminine traits perceived as stereotypic of entrepreneurs partly mediate their relationship on entrepreneurial intentions. Research limitations/implications The survey consists of cross-sectional, self-report data, and therefore the authors cannot conclusively infer causality. The direction of relationships found is of theoretical value. Only two countries are included in the sample limiting generalizability to other countries. Most of the participants in the sample reported some interest or experience in nascent entrepreneurial activities, which may limit the generalizability of findings to those without any prior interest or experience as a nascent entrepreneur. Originality/value The relationship between ambivalent sexism (both hostile and benevolent sexism) and both entrepreneurial intentions, and the gendered traits ascribed to entrepreneurs, has not yet been explored before this work. Using the lens of cultural masculinity, we present a theoretical model of how hostile and benevolent sexist attitudes facilitate or inhibit entrepreneurship via how entrepreneurs are perceived. This is the first study we know of which explores the relationship between Ambivalent Sexism and the gender attributes ascribed to entrepreneurs, and how these gendered entrepreneurial stereotypes in turn are related to entrepreneurial intentions.
Keywords: Ambivalent Sexism Scale; Benevolent sexism; Culture; Entrepreneurial intentions; Hostile sexism; Masculinity; Social construction of gender; dept.mgt; peer-reviewed

A Chinese–Canadian Cross-Cultural Investigation of Transformational Leadership, Autonomous Motivation, and Collectivistic Value - Wang, Zheni; Gagné, Marylène (Journal of Leadership & Organizational Studies, 2013)
Synthesizing theories of transformational leadership and self-determination, this research investigated whether transformational leaders (a) promote the autonomous motivation of their subordinates and whether (b) it results in higher autonomous motivation when subordinates hold high collectivistic values. Multilevel data were obtained from work samples in China and Canada. The results showed a positive relation between managers’ transformational leadership and subordinates’ autonomous motivation cross-culturally. Although higher collectivistic values were related to higher autonomous motivation, collectivist values did not significantly moderate the motivational effect of transformational leadership.
Keywords: dept.mgt; peer-reviewed

The Multidimensional Work Motivation Scale: Validation evidence in seven languages and nine countries - Gagné, Marylène; Forest, Jacques; Vansteenkiste, Maarten; Crevier-Braud, Laurence; van den Broeck, Anja; Aspeli, Ann Kristin; Bellerose, Jenny; Benabou, Charles; Chemolli, Emanuela; Güntert, Stefan Tomas; Halvari, Hallgeir; Indiyastuti, Devani Laksmi; et al. (European Journal of Work and Organizational Psychology, 2015)
Self-determination theory proposes a multidimensional conceptualization of motivation comprising autonomous and controlled forms. Whereas autonomous motivation relates positively to individuals’ optimal functioning (e.g., well-being, performance), controlled motivation is less beneficial. To be able to use self-determination theory in the field of organizational behaviour, the Multidimensional Work Motivation Scale was developed and tested using data from 3435 workers in seven languages and nine countries. Factorial analyses indicated that the 19-item scale has the same factor structure across the seven languages. Convergent and discriminant validity tests across the countries also indicate that the psychological needs for autonomy, competence, and relatedness as well as the theoretically derived antecedents to work motivation (e.g., leadership and job design) are predictably related to the different forms of motivation, which in turn are predictably related to important work outcomes (e.g., well-being, commitment, performance, and turnover intentions). Implications for the development of organizational research based on self-determination theory are discussed.
_eprint: https://doi.org/10.1080/1359432X.2013.877892
Keywords: Autonomous motivation; Controlled motivation; Cross-cultural; Extrinsic motivation; Intrinsic motivation; Self-determination theory; Validation; Work motivation; dept.mgt

Servant leadership and employee outcomes: the moderating role of subordinates’ motives - Donia, Magda B.L.; Raja, Usman; Panaccio, Alexandra; Wang, Zheni (European Journal of Work and Organizational Psychology, 2016)
Drawing from implicit leadership theories we advance servant leadership theory by examining moderating mechanisms that explain under what conditions servant leader behaviours impact followers in organizations. Specifically, we focused on the moderating role of subordinates’ motivational orientations—prosocial values or impression management motives—in relationships between servant leadership behaviours and job satisfaction, as well as subordinate organizational citizenship behaviours (OCBs). Using time-lagged data collected from 192 supervisor-subordinate dyads, we found that servant leadership was positively associated with employees’ job satisfaction, but not significantly related to their performance of OCBs. We also found evidence that subordinates’ motives moderate the relationships between servant leadership and outcomes. Specifically, employees high on impression management experienced lower levels of job satisfaction than their lower scoring counterparts. Our findings suggest that servant leadership may not be equally beneficial for all followers. We discuss implications for theory and practice.
_eprint: https://doi.org/10.1080/1359432X.2016.1149471
Keywords: citizenship behaviours; dept.mgt; employee motives; implicit leadership theories; job satisfaction; peer-reviewed; servant leadership

Genetically engineered food and genetically modified organisms - Nodoushani, Omid; Sintay, Jayme; Stewart, Carol (Competition Forum, 2015)
Keywords: dept.mgt; peer-reviewed

Organizations' investment in education - Nodoushani, Omid; Stewart, Carol; Escobar, Jessica (Competition Forum, 2016)
Keywords: dept.mgt; peer-reviewed

Cultivating Employees Using Maslow's Hierarchy of Needs - Stewart, Carol; Nodoushani, Omid; Stumpf, Jason (Competition Forum, 2018)
Stress caused by climates of fear in the workplace is sapping employee decision-making and causing conflict in the workplace. While hard to quantify, it is easy to understand why intelligent and engaged employees are the ideal: there are fewer mistakes and higher productivity. The primary metric used to frame the reasons for motivation is Maslow's Hierarchy of Needs. It is also vitally important to understand the power balance between employees and employers. By the very nature of employment, employers have less need for a particular employee unlike the employee who cannot afford to be unemployed.
Num Pages: 67-75 Place: Indiana, United States
Keywords: Business And Economics; Compensation; Competition; Corporate culture; Emotions; Employees; Employers; Employment; Employment security; Empowerment; Games; Handbooks; Happiness; Job satisfaction; Personal computers; Physiology; Software; Stress; Success; Work environment; Workers; dept.mgt; peer-reviewed

Surrounded by white water: Conflicts in management sciences regarding truth and reality - Stark, Ernie; Stepanovich, Paul; Poppler, Paul; Hopkins, Pamela J. (Journal of Behavioral & Applied Management, 2008)
Keywords: dept.mgt; peer-reviewed

A Clash of Capitalisms: Foreign Shareholders and Corporate Restructuring in 1990s Japan - Ahmadjian, Christina L.; Robbins, Gregory E. (American Sociological Review, 2005)
This article examines the clash between stakeholder- and shareholder-based business systems resulting from an increase in foreign portfolio investment in the Japanese economy during the 1990s. An analysis of 1,108 firms between 1991 and 2000 shows that as foreign institutional investors, who were more interested in investment returns than in long-term relationships, replaced domestic shareholders, one fundamental pillar of Japan's stakeholder capitalism began to crack. Japanese firms began to adopt downsizing and asset divestiture, practices more characteristic of Anglo-American shareholder economies. The influence of foreigners, however, was weaker in firms more deeply embedded in the local system through close ties to domestic financial institutions and corporate groups. Thus, foreign investors were influential primarily in firms less embedded in the existing stakeholder system. This research contributes to debates on globalization and convergence of business systems, institutional change, and corporate governance systems.
Keywords: dept.mgt; peer-reviewed

Sustainability and Embodiment: How Can You Be in Two Places at Once When You’re No Place at All? - Robbins, Gregory (Research Yearbook, 2012)
Keywords: dept.mgt; peer-reviewed

Sustainability initiatives: a competing values framework - Robbins, Gregory E.; Page, Mary A. (Competition Forum, 2012)
Keywords: dept.mgt; peer-reviewed

Hidden tradeoffs in sustainability initiatives - Page, Robert A; Robbins, Gregory (International Journal of Interdisciplinary Research, 2013)
Keywords: dept.mgt; peer-reviewed

Knowledge management and organizational performance in the service industry: The role of transformational leadership beyond the effects of transactional leadership - Birasnav, M. (Journal of Business Research, 2014)
This study examines a comprehensive model comprising of various relationships between transformational and transactional leadership, knowledge management (KM) process, and organizational performance. Data are collected from human resource managers and general managers working in 119 service firms. Exploratory factor analysis and hierarchical regression analysis are used to analyze the proposed hypotheses. The results indicate that transformational leadership has strong and positive effects on KM process and organizational performance after controlling for the effects of transactional leadership. Further, KM process partially mediates the relationship between transformational leadership and organizational performance after controlling for the effects of transactional leadership. Implications and directions for future research are also discussed.
Keywords: Knowledge management; Organizational performance; Transactional leadership; Transformational leadership; dept.mgt

Linking Leadership Behaviors and Information Exchange to Improve Supply Chain Performance: A Conceptual Model - Birasnav, M.; Mittal, Rakesh; Loughlin, Selene (Global Journal of Flexible Systems Management, 2015)
Organizations striving to improve cycle time concentrate on developing long-term relationship with suppliers. In order to support organizational efforts, this study develops a conceptual model that explores the relationships among leadership behaviors, relational commitment and trust, information exchange, and cycle time. Although the supply chain management literature mentions leadership behavior in the context of supply chain, there are no studies that examine the impact of leadership behaviors on cycle time. This study proposes that transformational and transactional leadership behaviors of buyers increase the flow of information to suppliers directly as well as indirectly through relational commitment and trust, and these relationships also influence cycle time. However, it also proposes that the impact of transformational leadership behaviors on relational commitment and trust and information exchange is stronger than the impact of transactional leadership behaviors. Additionally, both uncertain environment and supplier base have potential to play moderation roles in the relationship between transformational leadership and relational commitment and trust and between transformational leadership and information exchange.
Keywords: Cycle time; Information exchange; Relational commitment; Relational trust; Supplier base; Transactional leadership; Transformational leadership; dept.mgt; peer-reviewed

Mixed signals: do college graduates have the soft skills that employers want? - Stewart, Carol; Wall, Alison; Marciniec, Sheryl (Competition forum, 2016)
Keywords: dept.mgt; peer-reviewed

Bankruptcy Law and Practice - J.D, Grace A. Luppino; J.D, Robert A. Smith (Pearson, 2015)
Keywords: dept.mgt

Leadership, Generations and Small Business - Just, Renee (Scholars' Press, 2013)
Keywords: dept.mgt

Perspectives on Product Stewardship - Cassel, Scott (Bernan Press, 2023)
Keywords: dept.mgt

Sustainability and stratified noncompliance in the pharmaceutical industry - Page, Robert A.; Cyr, Danielle M.; Richardson, Anthony S. (Journal of International Business Disciplines, 2015)
Keywords: dept.bis; dept.mgt; peer-reviewed

Evaluating the Knowledge of Conversational Agents - Park, Mina; Aiken, Milam; Vanjani, Mahesh (Southwestern Business Administration Journal, 2019)
Keywords: dept.bis; dept.mgt; peer-reviewed

The Risks and Rewards of Computing Everywhere for Small Business Entrepreneurs. - Bassett, Richard A.; Richardson, Anthony S.; Page, Robert A. (Issues in Information Systems, 2015)
Keywords: dept.bis; dept.mgt; peer-reviewed

Gender Characterizations in Entrepreneurship: A Multi‐Level Investigation of Sex‐Role Stereotypes about High‐Growth, Commercial, and Social Entrepreneurs* - Gupta, Vishal K.; Wieland, Alice M.; Turban, Daniel B. (Journal of Small Business Management, 2019)
The purpose of this study is to cast new light on possible gender biases in implicit theories people hold about various forms of entrepreneurial activity. Using social role theory, we delve into sex‐role stereotypes associated with high‐ and low‐growth entrepreneurship and commercial and social entrepreneurship. Predictions were tested with an experimental design using both a between‐subject design to capture group‐level stereotypes and a within‐subject design to capture individual‐level stereotypes. Findings reveal that commercial and high‐growth entrepreneurs are perceived as more similar to men than to women and higher on agency than communality. Conversely, low‐growth entrepreneurs are perceived as more similar to women than men, and higher on communality than agency. Social entrepreneurs are uniquely perceived as similar to both men and women, though they are also considered higher on agency than communality. Interestingly, female, but not male respondents, perceive some overlap between the feminine gender role and high‐growth and commercial entrepreneurship. Notably, those higher on modern sexism perceive less overlap between entrepreneurship and femininity. Taken together, our results suggest that commercial high‐growth entrepreneurship is most strongly male‐typed, which is likely to be problematic for women (and non‐traditional men) wanting to start growth‐oriented ventures. Implications and directions for future research are discussed.
_eprint: https://www.tandfonline.com/doi/pdf/10.1111/jsbm.12495
Keywords: dept.mgt; peer-reviewed

Gendered cognitions: a socio-cognitive model of how gender affects entrepreneurial preferences - Wieland, Alice M.; Kemmelmeier, Markus; Gupta, Vishal K.; McKelvey, William (Understanding Women's Entrepreneurship in a Gendered Context, 2021)
Keywords: dept.mgt; peer-reviewed

Exploring the Gender Gap in Tech Companies: Why Aren't There More Women? - Chaudhry, Haroon; Wall, Alison E.; Wall, Jerry L. (Competition Forum, 2019)
Diversity issues in organizations have long been the subject of organizational studies and cultural examinations. While organizations have made several advancements to balance the presence of female representation in their employees, there remains a paucity of women in certain fields, most notably the tech industry where, despite similar performance in courses, women are alarmingly underrepresented. This paper examines this lack of diversity and proposes some remedies for specifically addressing the lack of women in the tech industry and can be extended to participation in any STEM careers that makes up a significant portion of the tech industry.
Num Pages: 275-280 Place: Indiana, United States
Keywords: Bullying; Business And Economics; Careers; Employees; Employment; Females; Gender; High tech industries; Litigation; Multiculturalism & pluralism; Research & development–R&D; STEM education; STEM professions; Social networks; Success; Women; dept.mgt; peer-reviewed

Staying Alive: Leadership in COVID-19 World - Stewart, Carol (Journal of Leadership, Accountability & Ethics, 2021)
While this unprecedented time of COVID-19 has resulted in financial loss for many companies, it's also produced new leadership opportunities. Remote work, at-home schooling, and socially-distancing are a few examples of the new norm and new business possibilities. As crisis proverbially breeds innovation, new businesses have already sprung up around the world in support of growing demands. History shows this growth in entrepreneurial endeavors to be a trend during times of economic downturn. More than half of 2009 Fortune 500 list and just under half of 2008's Inc. list were created during a recession or bear market. Challenging economic times often seed the growth of entrepreneurial capitalism. One reason for this growth is that startup companies begun during times of high stress tend to be capable of operating in less favorable conditions. In times of economic upheaval, even mature businesses with longer history and deeper pockets require special leadership to 'pivot' their operational strategies to stay viable. This paper explores effective leadership theories to explain the success during uncertain times.
Keywords: BEAR markets; COVID-19; LEADERSHIP; NEW business enterprises; SITUATIONAL leadership theory; TELECOMMUTING; dept.mgt; entrepreneurship; leadership; pandemic; peer-reviewed; pivoting; situational leadership

Business succession planning: a vital component to the success and longevity of small businesses - Smith Jr, Robert A.; Badr, Kauther S. (International Academy of Business Disciplines 24th Annual Conference, 2023)
Keywords: dept.mgt

Industrial Democracy in The Knowledge Society - Nodoushani, Omid; Robbins, Gregory Gadiel (Competition Forum, 2019)
Keywords: dept.mgt; peer-reviewed

Improving school performance and student academic orientation: the role of safety-oriented knowledge management and diversity - Birasnav, M.; Gantasala, Prabhakar Venugopal; Gantasala, Swapna Bhargavi (VINE Journal of Information and Knowledge Management Systems, 2021)
Purpose The purpose of this study is to examine the influence of the implementation of safety-oriented knowledge management (KM) processes and student diversity acceptance in schools and the interaction effect of safety-oriented KM processes and student diversity acceptance over school performance and student academic orientation. Design/methodology/approach Responses of 977 American schools available in the database of the National Center for Education Statistics were analyzed using hierarchical regression analyses. Findings Results show that implementation of safety-oriented KM processes and diversity acceptance in schools have varying effects on school performance and student academic orientation. The impact of knowledge acquisition from parents on the academic achievement of students is positive and stronger in schools that are low in student diversity acceptance than schools that are high in student diversity acceptance. Originality/value This study adds value to the KM literature by exploring how KM processes are executed in American schools to improve their performance and students’ academic orientation and how diversity among students alters the strength of the relationships.
Keywords: Diversity acceptance; Knowledge management processes; School performance; School safety; Student academic orientation; dept.mgt; peer-reviewed

Supply chain integration, advanced manufacturing technology, and strategic leadership: An empirical study - Birasnav, M.; Bienstock, Joshua (Computers & Industrial Engineering, 2019)
Top management support is a crucial investment at any manufacturing firm striving to integrate supply chain partners with the manufacturing processes so as to achieve a competitive advantage. Though the effectiveness of different leadership behaviors exhibited in top-level management has been documented in the leadership literature, the influence of such behaviors on developing linkages with supply chain partners has not been extensively examined. In order to bridge this research gap, this study examines the interlinkages between strategic leadership theory and supply chain integration theory. In addition, it also investigates the interrelationships between these two theories in the context of implementation of advanced manufacturing technology. Data has been collected from 107 small manufacturing companies and was analyzed using structural equation modelling. Results show that transactional leadership exhibited in top-level management is positively related to internal integration within the manufacturing companies. Transformational leadership behavior exhibited in top-level management and advanced manufacturing technology implemented in the shop floor of these companies are positively related to the integration of external supply chain partners. In addition, we also found that in those instances where small manufacturing companies place a high emphasis on the implementation of advanced manufacturing technology, they are guided by transformational leaders who strongly integrate their companies with customers.
Keywords: Advanced manufacturing technology; Customer integration; Internal integration; Small manufacturing industries; Strategic leadership; Supplier integration; dept.mgt; peer-reviewed

Integration of Social Capital and Organizational Learning Theories to Improve Operational Performance - Birasnav, M.; Chaudhary, Richa; Scillitoe, Joanne (Global Journal of Flexible Systems Management, 2019)
This study focuses on integrating the premises of social capital theory and the theory of organizational learning to improve the operational performance of firms nurturing the buyer–supplier relationship. Social capital theory highlights the importance of developing social relationships between firms to create valuable resources and collectively access critical resources. Organizational learning theory highlights that the learning capacity of an organization strongly depends on top-level leaders’ behaviors, organizational structure, culture, and flexibility, and uncertainties in the environment in which the organization functions. Though many studies have focused on the impact of social capital on performance improvements in the buyer–supplier relationship, the interlinkages between social capital and organizational learning have not been given much attention. Based upon these theories, a system-focused perspective, which showcases the antecedents and outcome of the relationship between collaborative communication and learning, has been proposed in this study. A literature review has been carried out to support the linkages in the proposed conceptual model. Findings suggest that transformational buyers support creating cognitive capital with suppliers. This cognitive capital influences the structural capital, which supports improving the understanding of each party’s processes in the buyer–supplier relationship when parties have high long-term orientation. Improved learning capability reshapes organizations into flexible systems capable of responding quickly to customer requirements, and consequently, they realize a higher performance level.
Keywords: Collaborative communication; Information technology competency; Long-term orientation; Organizational learning; Supplier knowledge; Transformational leadership; dept.mgt

Integrating Theories of Strategic Leadership, Social Exchange, and Structural Capital in the Context of Buyer–Supplier Relationship: An Empirical Study - Birasnav, M.; Mittal, Rakesh; Dalpati, Avadhesh (Global Journal of Flexible Systems Management, 2019)
This study is aimed at improving the purchasing cycle time in a buyer–supplier relationship by integrating the facets of strategic leadership, social exchange, and social capital theories. We developed and tested a conceptual model that postulated relationships among strategic leadership behavior, relational trust and commitment, structural capital, and purchasing cycle time. Data were collected from purchase managers and their employees working in 105 manufacturing companies and analyzed using structural equation modeling technique. Our findings indicated that strategic leadership behaviors are positively related to trust in the buyer–supplier relationship. In addition, trust enhances relational commitment between buyer and supplier, which in turn positively relates to information sharing and supplier development. Further, increased information sharing in the relationship results in reduced purchasing cycle time. Implications for both theory and practice are discussed in depth, and directions for future research are suggested.
Keywords: Cycle time; Information sharing; Relational commitment; Relational trust-Strategic leadership; Supplier development; dept.mgt; peer-reviewed

Routing vehicles through cross-docking facility for third party logistics service providers - Birasnav, M.; Kalaivanan, S.; Ramesh, A.; Tibrewala, Rajendra (International Journal of Operational Research, 2020)
This study focuses on a specialised vehicle routing problem (VRP) to transport matchboxes from manufacturing companies to retailers through a cross-dock (cross-docking facility) operated by a third party logistics service provider. Three processes (unloading, consolidating, and loading) are carried out at a cross-dock for completely avoiding or keeping inventory for a very short time. The specialised VRP, addressed in this paper, consists of multiple suppliers (each supplier can produce different brands of products for any number of customers) and multiple customers (each customer can receive orders from any number of suppliers). A mixed integer linear programming model has been developed to solve this kind of NP-hard problem. The objective of this model is to minimise total cost incurred in picking up and transporting the matchboxes from the manufacturers to cross-dock, consolidating matchboxes at cross-dock, and in transporting and delivering the matchboxes to the customers. This study also proposes an effective heuristic procedure to solve the same problem and compares the solution obtained using the heuristic procedure to the optimal solution obtained using the exact method. The findings show that the heuristic method, proposed by us, generates near optimum solutions using significantly less computational time than the exact method.
Keywords: NP-hard; consolidating; cross-docking; dept.mgt; heuristic; logistics service provider; multiple customers; multiple suppliers; peer-reviewed; vehicle routing

Performance evaluation of geospatially assisted reference evapotranspiration models - Pandi, Dinagarapandi; Saravanan, Kothadaramanan; Kuppusamy, Mohan; Birasnav, M. (Arabian Journal of Geosciences, 2022)
Mapping of spatiotemporal distribution of evapotranspiration becomes important for sustainable water management as water scarcity is nowadays a growing concern in almost all the continents. In general, researchers estimate evapotranspiration by multiplying the computed reference evapotranspiration (ETo) with the corresponding crop coefficient. Such estimation of ETo requires data related to spatiotemporal meteorological and vegetation field characteristics, and however, these data are rarely available in most developing countries such as India. Thus, researchers constantly develop various methods and evaluate the applicability of these methods to accurately capture spatiotemporal distribution. The purposes of this study are to (a) examine the applicability of Hargreaves and MODIS ETo method to map the spatiotemporal distribution over Thamirabarani basin located in Southern India and (b) evaluate the performances of Hargreaves and MODIS ETo methods and compare it to FAO 56 Penman–Monteith method. To achieve these purposes, ETo data of Hargreaves method and MODIS ETo method over Cheranmadevi meteorological observatory are extracted and performances of these methods are compared with FAO 56 Penman–Monteith method. Results show that a match exists among all the three ETo datasets, and no major deviations have been observed. However, this study suggests local calibration of Hargreaves and MODIS ETo method as considerable mismatch has been observed at ETo daily value. Overall, the conclusion of this study encourages the application of the Hargreaves method and MODIS ETo method in developing countries, where the data shortage condition prevails.
Keywords: Evapotranspiration; FAO 56 Penman–Monteith method; Hargreaves method; MODIS ETo; Thamirabarani basin; dept.mgt; peer-reviewed

Green supply chain management: A theoretical framework and research directions - Birasnav, M.; Chaudhary, Richa; Henry Dunne, James; Bienstock, Joshua; Seaman, Cristina (Computers & Industrial Engineering, 2022)
Practitioners and academicians dedicate significant attention to tackling initiatives and executing mechanisms to address society’s environmental concerns. Further, organizations and researchers recognize that there is a need to implement green supply chain management (GSCM) practices as a part of green strategy. To date, embedding a sustainability dimension into supply chain management remains a challenge for organizations given the lack of systematic knowledge of the key dimensions of GSCM practices, the factors that influence the implementation of GSCM practices, and the benefits that organizations gain through the implementation of such practices. To address this problem, this study reviews 151 research articles published between 1997 and 2021 in the GSCM literature, and offers a theoretical framework that synthesizes and integrates the knowledge acquired from the reviewed literature. This framework includes various dimensions of GSCM practices identified in the past research studies, the antecedents that influence implementation of GSCM practices, and the outcomes of implementation of such practices. Further, this study offers theoretical and practical perspectives to support future research utilizing a research model as a baseline to guide organizations in the understanding of the primary GSCM attributes, their predictors, and benefits.
Keywords: Antecedents; Green supply chain; Outcomes; Systematic literature review; dept.mgt; peer-reviewed

Ease of market entry of Indian startups: formal and informal institutional influences - Scillitoe, Joanne L.; Birasnav, Muthuraj (South Asian Journal of Business Studies, 2021)
Purpose The purpose of this study offers a theoretical model, hypotheses and empirical analyses of how formal and informal institutions influence the ease of market entry of startups in the context of India. Design/methodology/approach A theoretical model based upon institutional and market entry theories is presented with hypotheses. Structural equation modeling is used to test the hypotheses. Findings Results of the study suggest that college preparations and a culture of creativity and innovation are positively related to ease of market entry by Indian startups. A culture of personal success is negatively related to ease of market entry. Government assistance related to ease of market entry is not significant. Originality/value This paper offers a new perspective, linking formal and informal institutional influences to startup ease of market entry. In addition, informal institutions are viewed from the cultures of personal success and creativity/innovation within the entrepreneurial domain, which is also new to the literature. This paper offers specific insights in the context of India startups and offers some interesting findings that can contribution to the literature, policy and practice.
Keywords: Culture; Entrepreneurship; India; Institutions; Market entry; Startup; dept.mgt; peer-reviewed

Total quality leadership and organizational innovativeness: the role of social capital development in American schools - Birasnav, M.; Gantasala, Swapna Bhargavi; Gantasala, Venugopal Prabhakar; Singh, Abhishek (Benchmarking: An International Journal, 2022)
Purpose The purpose of this study is to explore the relationship between total quality leadership, social capital development and organizational innovativeness in the school environment. While there are research studies focused on the impact of leadership on implementing quality management practices, innovation and organizational performance, the mediating effect of social capital development has not been explored on the influence of the school leaders. Design/methodology/approach To achieve the purpose of this study, data collected from 158 principals, who participated in the Teaching and Learning International Survey 2018, were analyzed using structural equation modeling. Findings This study found that total quality learning-oriented school leaders are supportive of developing social capital in their schools, and such social capital development is very useful to improve organizational innovativeness. Interestingly, social capital development has been found to mediate the relationship between total quality learning-oriented school leadership and organizational innovativeness. Practical implications This study submits evidence for two major activities that school leaders perform: learning- and control-oriented activities, both being important for improving and measuring quality in the educational sector. This study clearly shows that control-oriented activities lean toward negatively on social capital while learning-oriented activities strongly and positively influence social capital development. From this study, practitioners can be aware and consciously promote social capital development in schools and that social capital development mediates the influence of total quality leadership and innovation in schools. Originality/value Schools can be visualized as guarded communities for creating a secure environment for students in support of learning. This research study shows that the combined cognitive capital, structural capital and relational capital mediate the impacts of total quality leadership on innovativeness in schools. Thus, school leaders should first establish a mechanism to develop social capital among their employees to bring up innovative initiatives.
Keywords: Organizational innovativeness; School leaders; Social capital; TALIS; Total quality leadership; dept.mgt; peer-reviewed

Cash Holdings and Firm Performance in the Restaurant Industry - Kim, Jung Hoon; Lim, Jaeseong; Ahn, Jin Sun; Kim, Youngbin (Journal of Applied Business and Economics, 2023)
This study explores the link between cash holdings and performance outcomes in public restaurant companies in the United States, leveraging the critical role played by the industry context. We hypothesize that cash holdings have positive associations with both short-term and long-term firm performance in the restaurant industry. Our empirical analyses, based on fixed-effect regression models that control for all time-invariant variables, reveal that holding cash can improve performance in the restaurant industry, in support of our hypotheses.
Number: 3
Keywords: dept.mgt; firm performance; peer-reviewed

Money and Morality: Leadership in the National Football League - Stewart, Carol; Joyner-McGraw, Laquita (Competition Forum, 2019)
Keywords: dept.mgt; peer-reviewed

Recruiting and Retaining the Genius Generation for Virtual Teams from a Generation Z Perspective - McGraw, Laquita; Stewart, Carol (International Journal of Business Research & Information Technology (IJBRIT), 2020)
The concept of a virtual team is expanding as its application is growing with multiple generations in the workforce. A virtual team is now a significant issue in the 21st century because there are currently five generations in the workforce. To lead a multigenerational virtual team, employers must understand a new generation that is entering the workplace. Although Generation Z will bring new characteristic to the workforce, leadership styles must transform to accommodate a newer generation's expectations. This study explores leadership styles to support virtual teams and a new generation. There exist only a few qualitative studies on virtual teams in today's domestic workforce. The researchers wish to gain knowledge of which leadership style works for a virtual team from the perspectives of Generation Z.
Keywords: GENERATION Z; GENIUS; Generation Y; Generation Z; LEADERSHIP; TEAMS; VIRTUAL communities; VIRTUAL work teams; Virtual team; dept.mgt; leadership; peer-reviewed

Leadership and Corporate Social Responsibility in Sports: If You’re Not First, You’re Last - Stewart, Carol; Marciniec, Sheryl; Joyner-McGraw, Laquita; Han, Seungmin (International Journal of Business and Public Adminstration, 2020)
Keywords: dept.mgt; peer-reviewed

Characteristics of Effective Trade Secrets and Confi dential Information Policies: Guidance from Labor Arbitration Cases - Ross, William H.; Franklin, Danny (Labor Law Journal, 2020)
In an effort to craft recommendations to managers regarding effective confidential information policies, the present paper reviewed 88 published grievance arbitration cases involving proprietary information, trade secrets, and confidential information. Most cases dealt with the application of managerial discipline for employee violations of company polices and collective-bargaining provisions. Themes that emerged included: the importance of a Management Rights clause (as well as specific Misconduct clauses and policies), clauses that address changing business conditions (such as subcontracting and new technology), employee insubordination, theft, falsification, conflict of interest, and the need for training. Additionally, arbitrators often considered specific laws that apply in health care, cable television, and telecommunications industries. Finally, several mitigating factors were noted such as: having permission from a supervisor to access confidential information, safety, and whistleblowing concerns. By attending to factors that influence arbitrator decision making, managers and their attorneys can use these identified factors to create better policies and negotiate robust collective bargaining provisions.
Num Pages: 43-57 Place: Riverwoods, United States Publisher: CCH Incorporated: Health & Human Resources
Keywords: Arbitration; Business And Economics–Labor And Industrial Relations; Collective bargaining; Competition; Competitive advantage; Conflicts of interest; Discipline; Employees; Espionage; Fair & Accurate Credit Transactions Act 2003-US; Information policies; Intellectual property; Labor law; Law; dept.mgt

Advice-Taking in Ethical Dilemmas - Franklin, Danny; Guerber, Amy J. (Editorial Policy, 2020)
Keywords: dept.mgt; peer-reviewed

The Reciprocal Relationship between Containers Overboard and Climate Change - Daniel, J.; Stapleton, K. A.; Stapleton, D.; Nandialath, A.; Franklin, D. (Journal of Transportation Law, Logistics, and Policy, 2021)
Not only does the flotsam and jetsam in the world’s oceans seem to be impacting the health of the world’s oceans and seas, but it appears that the warming climate and increasing CO2 emissions are impacting the global trade lanes evidenced by a greater-than-average number of lost maritime containers due to resultant rougher seas and stronger storms. We elucidate the evolution of containerized shipping and discuss the impact lost containers have on the seas and dangers to other ocean-going vessels. We also note the reciprocal effects between climate change and lost containers. The intent of our article is to shed light on these issues and we hope it sparks future research examining causal factors and their potential solutions.
Keywords: dept.mgt; peer-reviewed

Employee Assistance Programs: Balancing Increased Productivity and Engagement Among Employees with Equal Employment and Legal Complience - Smith, Robert A.; Badr, Kauther S.; Wall, Alison E. (Competition Forum, 2019)
Managing the impact of employees' personal and work-related difficulties on workplace productivity is becoming increasingly salient for organizations. Employee Assistance Programs (EAPs) are one approach to help improve the quality of life for employees and maximize their productivity. While EAPs have many benefits, potential negative ramifications and legal considerations must also be considered. This article highlights some important cases and the best practices for organizations to utilize in creating clear organizational policies that align with equal employment opportunity and privacy laws in collaboration with legal and human resources professionals and employee assistance providers to reduce or eliminate potential liability.
Num Pages: 232-239 Place: Indiana, United States
Keywords: Absenteeism; Affirmative action; Business And Economics; Complaints; Confidentiality; Costs; Employees; Employers; Employment discrimination; Human resource management; Labor law; Performance evaluation; Productivity; Sexual harassment; dept.mgt; peer-reviewed; ⛔ No DOI found

Home Address Exemptions in State FOI Laws - Gil, Jodie; Smith, Robert A.; Badr, Kauther S. (The Journal of Civic Information, 2022)
Number: 4
Keywords: dept.mgt; peer-reviewed

Towards an integrated understanding of art, spirituality, and well-being - Yang, Charlie (Journal of Management, Spirituality & Religion, 2023)
Keywords: dept.mgt; peer-reviewed

The Escalating Competition Faced by Netflix - Jin, Sun Ahn; Jung, Hoon Kim; Youngbin, Kim; Jaeseong, Lim (Journal of Accounting-Business dan Management, 2023)
Num Pages: 1
Keywords: dept.mgt; peer-reviewed

The Effect of Market-Entry Timing on a Firm’s Speed and Cost of Entry - Lee, Minjae (American Journal of Management, 2023)
This paper examines the effect of market-entry timing on a firm’s speed and cost of entry in a setting where a firm needs to build a plant for market entry. Based on our developed analytical model, we provide seven scenarios of the market-entry timing effect on a firm’s entry speed and cost. We test hypotheses in the liquefied natural gas (LNG) industry. We use Wooldridge’s three-step instrumental variable (IV) approach to account for endogeneity bias. We find that a late entrant has (1) a shorter time-to-build and (2) a higher cost-to-build relative to an early entrant. Further, (3) the late entrant positively moderates the negative relationship of time-to-build and cost-to-build (i.e., the negative relationship of time-to build and cost-to-build becomes less negative for the late entrant). These empirical results are consistent with the prediction of when both revenue effect (i.e., revenue curve shift) and cost effect (i.e., cost curve leftward shift) exist.
Number: 3
Keywords: dept.mgt; peer-reviewed; time compression diseconomies

Developing the Construct of Speed Ceteris Paribus - Lee, Minjae (Academy of Management Proceedings, 2023)
Firm speed has long been a construct of interest among managers and researchers. Despite its importance, making a ceteris paribus comparison of speed can be challenging. In the current paper, we suggest an alternative to the conventional way of capturing the speed ceteris paribus. First, we illustrate the concept of faster speed in strategic management research. Second, we use numerical simulation data to illustrate the challenges of the conventional methodology, known as the nonlinear transformation of variables. We show that this method is difficult to apply and may produce an inaccurate measurement of the concept unless the exact functional form is chosen. Third, we suggest an alternative methodology, known as data envelopment analysis. This accounts for the challenges of the conventional methodology when we do not know the accurate functional form for nonlinear transformation, while performing as well as the best of the conventional approach. Finally, by using actual firm data, we show that our suggested methodology can be an effective alternative to the conventional approach of capturing a firm’s speed.
Keywords: AOM Annual Meeting Proceedings 2023; AOM Boston 2023; Research Methods; dept.mgt

When Does an Increase in a Firm’s Operational Effectiveness Reduce its Economic Performance? - Lee, Minjae (Academy of Management Proceedings, 2023)
Conventional wisdom suggests that an increase in a firm’s operational effectiveness will increase its economic performance. However, we show that an increase in a firm’s operational effectiveness can decrease its economic performance. Specifically, a firm’s increase in operational effectiveness of its existing projects following a positive demand shock can limit its profitable growth as its strategic resources are not allocated to pursuing new projects, thereby incurring opportunity costs that can lower its economic performance. We corroborate this reasoning in the context of the liquefied natural gas industry, which experienced a positive demand shock in 2000 due to energy market liberalization. We find empirically that a firm’s operational effectiveness increases its Tobin’s Q in the pre-shock period and reduces it in the post-shock period.
Keywords: AOM Annual Meeting Proceedings 2023; AOM Boston 2023; Strategic Management; dept.mgt

Understand the changes in motivation: comparative studies using theory-based interventions - Wang, Zheni; Briand, Melanie (Academy of Management Proceedings, 2023)
Managers often need to stay motivated and effectively motivate others. Therefore, they should rely on evidence-based interventions to manage the daily routine of motivational dynamics at work. This research answered how self-determination-theory-based interventions change employees’ motivation and motivational consequences during short time frames (i.e., within an hour, within a few weeks/months). Field study one focused on assessing the effectiveness of a one-day training workshop in helping improve managers’ work motivation, basic psychological needs satisfaction/frustration, and changing managers’ needs-supportive/thwarting behaviors within a few weeks. Results supported the training effectiveness as managers were rated less needs-thwarting by their direct subordinates and self-reported improvement in needs satisfaction/frustration six weeks after completing the training program. Online study two used the mean and covariance structure analysis and tested the three types of basic psychological needs supportive/thwarting and control conditions (3x2x1 factorial design) on the situational motivation, vitality, and general self-efficacy for playing online word games within 30 minutes. Multi-group confirmatory factor analysis (CFA) confirmed the scalar measurement invariance, then latent group means comparison results showed consistently lower controlled motivation across the needs-supportive and thwarting experimental conditions. During a quick online working scenario, the theory-based momentary intervention effectively changed situational extrinsic self-regulation in Amazon MTurk participants. Supplementary structural equation modeling (SEM) analyses using experience samples supported the indirect dual-path model from basic needs satisfaction to vitality and general efficacy via situational motivation. We discussed the theoretical implications of the temporal properties of work motivation, the practical implications on employee training and organizational change programs, and the limitations.
Keywords: AOM Annual Meeting Proceedings 2023; AOM Boston 2023; Organizational Behavior; dept.mgt

What explains the spread of corporate social responsibility? The role of competitive pressure and institutional isomorphism in the diffusion of voluntary adoption - Han, Seungmin; Ito, Kiyohiko (Journal of Management & Organization, 2023)
This study provides a new perspective on the determinants of the spread of voluntary corporate social responsibility (CSR) adoption by incorporating the potential role of its adoption by industry competitors. We find supportive evidence that firms make CSR adoption decisions in response to competitive pressure as well as institutional mimetic pressures. Based on an event history analysis of longitudinal data from a sample of 711 Korean publicly traded firms over a 12-year period, our findings suggest that the CSR behavior of competitors is positively associated with a focal firm's earlier adoption of CSR, leading to the diffusion of CSR across firms. Specifically, this study shows that the pure rivalry-driven pressure from non-leader competitors has a stronger positive relationship with earlier CSR adoption. The results also indicate that a firm's CSR adoption decision is accelerated by competitive rivalry as well as social pressures arising from institutional mimetic isomorphism.
Keywords: Competitive strategy; corporate social responsibility; dept.mgt; institutional theory; peer-reviewed; quantitative methods

The Evolving Landscape of International Consumer Data Privacy Compliance. - Pisano, Mark; Smith, Robert A.; Badr, Kauther S. (ACET Journal of Computer Education & Research, 2022)
Keywords: dept.bis; dept.mgt; peer-reviewed; ⛔ No DOI found

The Crisis of Danbury Fair Mall - Ahn, Jin Sun; Chung, Hanyong; Kim, Jung Hoon; Kim, Youngbin; Shin, Natalie Jungyoun (Journal of Marketing Development and Competitiveness, 2021)
This case describes the difficult financial situation of Danbury Fair Mall, which is the second biggest shopping mall in Connecticut. After World War II, the shopping mall business had grown fast especially in suburban areas of the U.S. However, the increasing popularity of online shopping caused extensive damage to shopping malls. This case will provide students the chance to think about the past, the present, and the future of the shopping mall industry in the U.S
Number: 2
Keywords: Connecticut; dept.acc; dept.mgt; peer-reviewed; ⛔ No DOI found

Arts-based pedagogy in management education: personal reflections - Yang, Charlie; Ivanova, Ekaterina; Ivanova, Maria (Honing Self-Awareness of Faculty and Future Business Leaders: Emotions Connected with Teaching and Learning, 2023)
Historically business education has put greater emphasis on rational analysis and the acquisition of instrumental and technical knowledge, while paying relatively scant attention to developing business students’ soft skills such as self- and social awareness and emotional intelligence through contemplative learning. In light of the growing need for more open and diverse ways of knowing that are more holistic, emotional, and aesthetic in management education, the authors present a 2 × 2 framework of arts-based pedagogy which helps organize various arts-based practices currently used in management education. The authors also share their personal reflections on using artful practices, specifically focussing on two individual-level experiential learning activities (i.e. museum visits and e-portfolio projects) and one group-based participatory art project. The authors further discuss why creative thinking and innovative arts-based practices can open up a new possibility for filling the gaps in current management education, especially in regard to developing students’ self- and social awareness and environmental consciousness in a more creative manner.
Keywords: Arts-based pedagogy; Digital photography; Electronic portfolio (e-portfolio); Museum learning; Participatory art; Socially engaged art; dept.mgt

Using Action Research to Build a Learning Organization in a New School of Pharmacy. - Hopkins, Pamela (2010)
Keywords: dept.mgt; faculty_collection; sabbatical_report

The Role of Chance in CEO Selection. - Stepanovich, Paul (2010)
Keywords: dept.mgt; faculty_collection; sabbatical_report

The Evolution and Commercialization of Wind Power Technology. - Laird, Kenneth R. (2005)
Keywords: dept.mgt; faculty_collection; sabbatical_report

Riga, Latvia Sabbatical Leave. - Frank, Ellen J. (2003)
Keywords: dept.mgt; faculty_collection; sabbatical_report

[Teaching, Learning and Researching Experiences] - Kidney, James (1999)
Keywords: dept.mgt; faculty_collection; sabbatical_report

Integration of Computer Usage in Management and Law Courses. - Prasad, Durga (1993)
Keywords: dept.mgt; faculty_collection; sabbatical_report

Daily Business Etiquette. - Frank, Ellen (1992)
Keywords: dept.mgt; faculty_collection; sabbatical_report

Empower! To Win: An Action Guide to the Imperative Leadership Style of the 21st Century - Brady, Gene F. (Xlibris Corp., 2009)
Keywords: Leadership; dept.mgt

Leadership as Place - Beatty, Ellen; Page, Robert (Leadership in Place: How Academic Professionals Can Find Their Leadership Voice, 2007)
Keywords: Administration; Universities and colleges; Faculty; Educational leadership; United States; Universities and colleges; dept.aa; dept.mgt; faculty_collection

Historical Encyclopedia of American Women Entrepreneurs: 1776 to the Present - Oppedisano, Jeannette M. (Greenwood Press, 2000)
Keywords: Biography; Businesspeople; Biography; Businesswomen; Businesswomen; Encyclopedias; Encyclopedias; Businesspeople; History; United States; dept.mgt; faculty_collection

Introduction to Business Law and Ethics - Badr, Kauther S.; Smith Jr, Robert A. (Kendall Hunt, 2022)
Keywords: dept.mgt

A Longitudinal Investigation of the Changes in Work Motivation and Employees’ Psychological Health - Wang, Zheni; Panaccio, Alexandra (Administrative Sciences, 2022)
Organizations strive to motivate employees to thrive at work. However, employees’ motivation is likely to vary over a short period (e.g., a few months) to cope with the routine dynamics of organizations’ activities. These motivation dynamics covary with employees’ affective, cognitive, and behavioral outcomes in the workplace. Moreover, employees’ psychological health, a multidimensional concept focused on the individual’s well/ill-being simultaneously, changes over time. Using the integrated theoretical frameworks of self-determination theory (SDT) and the hierarchical model of self-determined motivation (H-SDT), this research sought to examine the motivational changes following the dual-path model. In particular, this work sought to unpack the temporal dynamics in employees’ subjective well/ill-beings predicted by the changes in basic needs satisfaction/frustration through autonomous/controlled motivation, while considering the characteristics of people’s general causality orientations (trait-level motivation). Over four months, longitudinal field data were collected from the employees in several private small businesses in the consumer product retail industry. Latent growth modeling (LGM) results supported the positive dual relations between the changes in employees’ psychological health and basic psychological needs satisfaction/frustration, but neither the changes of autonomous/controlled work motivation nor the indirect change paths via autonomous/controlled work motivation were significant. Finally, we discussed the theoretical and practical implications of the findings. Limitations and possible future research directions to further this line of research on the dynamic of work motivation were also summarized.
0 citations (Crossref) [2023-10-31] Number: 4
Keywords: change in motivation; dept.mgt; longitudinal study; peer-reviewed; psychological health

Thriving in the dynamics: a multi-level investigation of needs-supportive features, situational motivation, and employees’ subjective well-being - Wang, Zheni; Panaccio, Alexandra (Current Psychology, 2023)
Employees often demonstrate various regulatory intentions toward multiple responsibilities they must fulfill on the job. Therefore, it is possible that employees’ motivation changes during the workday because of the various situations they have experienced and that these motivational fluctuations affect their subjective well-being across different activities. Following the integrated frameworks of the self-determination theory (SDT) and the hierarchical model of motivation (H-SDT), the present research studied the variations of employees’ daily motivation for work across different activities using the survey of day reconstruction method (DRM). Multi-level structural equation modeling (MSEM) was used to analyze the variations in the perceived three basic psychological (i.e., autonomy-, relatedness-, and competence-) needs-supportive features (NSFs), situational motivation, and variables capturing the employees’ subjective well-being (including vitality and positive/negative affect) laid out according to a list of work episodes in DRM. Results of this study confirmed that employees’ subjective well-being (mainly vitality and positive affect) were positively promoted by NSFs pertained to specific work activities via the indirect path of situational autonomous motivation at work. Furthermore, vitality and positive affect were also directly predicted by situational autonomous motivation. These empirical findings expanded the research evidence supporting employees’ subjective well-being as a multi-level and multi-dimensional dynamic motivational consequence promoted by configurable specific NSFs at work. We also discussed the limitations and future directions for this line of research.
Keywords: Dynamics of work motivation; Multi-level modeling; Psychological health; dept.mgt; peer-reviewed

Energy transitions and labor market patterns in the U.S. coal industry - Michieka, Nyakundi M.; Graziano, Marcello; Musso, Marta; Fouquet, Roger (Structural Change and Economic Dynamics, 2022)
The U.S. coal industry is in the midst of a transition. Changes in regulation and technological innovation from other fossils and renewables have affected its competitiveness. These could have significant impacts on the labor market where jobs could be lost. In this study, we investigate how changes in employment in the coal industry affect wages in 20 industries in 10 U.S. coal producing states. We assess how these transitions impact welfare programs, since coal producing regions are associated with higher poverty levels. Results show that in the long run, migration of coal workers decreased wages in the construction, manufacturing sectors. Point estimates reveal that an increase in separations of coal workers increase Supplemental Nutrition Assistance Program (SNAP) caseloads. In states where coal mining has a smaller contribution to GDP, an increase in coal employment increases SNAP caseloads.
7 citations (Crossref) [2023-10-31]
Keywords: Labor market dynamics; dept.mgt; peer-reviewed

The spatial dimension of energy transition policies, practices and technologies - Caragliu, A.; Graziano, M. (Energy Policy, 2022)
2 citations (Crossref) [2023-10-31]
Keywords: dept.mgt; peer-reviewed

Servant leadership and employee wellbeing: A crosscultural investigation of the moderated path model in Canada, Pakistan, China, the US, and Brazil - Wang, Zheni; Panaccio, Alexandra; Raja, Usman; Donia, Magda; Landry, Guylaine; Pereira, Michelle Morelo; Ferreira, Maria Cristina (International Journal of Cross Cultural Management, 2022)
Drawing on samples from Canada, Pakistan, China, the US, and Brazil comprising over 800 employees, we examined whether servant leaders (SL) - characterized as putting the needs of others above their own - promote employees’ well-being via autonomous motivation, accounting for employees’ power distance and collectivism values as moderating variables. Autonomous motivation, a type of self-regulation, sustains one’s well-being. Personal values facilitate one’s work behaviors cross-culturally. Multigroup confirmatory factor analysis (CFA) results confirmed matrix invariance of all the measures. The path and moderation analyses result using multilevel structural equation modeling (SEM) supported the positive direct and indirect paths among SL, autonomous motivation, and psychological well-being across the five cultures; Collectivistic value negatively moderated the relationship between servant leadership and autonomous motivation across the Chinese and US samples. In addition, with only a limited number of items, measurements of SL and vitality achieved scalar invariance. ANOVA test results also confirmed the significant comparative differences in these two variables among the cultural groups. Findings in this research provided robust and empirical support for the motivational effects of the servant leadership theory across the globe. Theoretical and practical implications for evidence-based cross-cultural management practices and future directions for leadership training in diverse cultural contexts are discussed.
0 citations (Crossref) [2023-10-31]
Keywords: Servant leadership; autonomous motivation; dept.mgt; peer-reviewed; personal values; psychological well-being

A Data-Driven Algorithm to Redefine the U.S. Rural Landscape: Affinity Propagation as a Mixed-Data/Mixed-Method Tool - Heumann, Benjamin W.; Graziano, Marcello; Fiaschetti, Maurizio (Economic Development Quarterly, 2022)
This study demonstrates the application of affinity propagation as a data-driven approach to identifying and mapping typologies of place along the urban-rural continuum. The authors characterize Zip Code Tabulation Areas using demographic, economic, land cover, and accessibility to transportation infrastructure, which results in 22 clusters, 15 of which have a major rural component. The spatial pattern of these clusters varies, reflecting the heterogeneity in U.S. rurality. Rural is not a single concept that can be simply defined by population density. By comparing three economic indicators before and after the global financial crisis of 2007 to 2012, the authors find that the degree of economic recovery is captured by rural typologies. They compare both the methodological results and analysis of socioeconomic resilience to two of the most used threshold-based regional typologies, one developed by the U.S. Department of Agriculture Economic Research Service and one used by the American Communities Project.
0 citations (Crossref) [2023-10-31]
Keywords: dept.mgt; peer-reviewed; rural data; rural demography; rural development

The many sizes and characters of the Blue Economy - Graziano, M.; Alexander, K.A.; McGrane, S.J.; Allan, G.J.; Lema, E. (Ecological Economics, 2022)
This article analyses the economic size and resilience of five established definitions of the Blue Economy across two geographical locations: Scotland (UK) and Michigan (USA). The article analyses sector-level employment, labor productivity and Gross Value Added (GVA) data, and uses graphical representations to highlight the differences in conceptualizing the Blue Economy in ways that affect its weight and contribution to regional economies. Further, it analyses how each definition has fared in the post-2007/2011 crisis, assessing their resilience. This novel work tackles the emerging discourse around the Blue Economy by highlighting its regional character, and by problematizing the divergent definitions of the concept. © 2022 Elsevier B.V.
6 citations (Crossref) [2023-10-31]
Keywords: Blue Economy; Employment; Regional analysis; Wages; dept.mgt; peer-reviewed

Managerial resistance to change: Romania’s quest for a market economy - Catana, D.; Catana, A.; Finlay, J.L. (Journal of East European Management Studies, 1999)
This exploratory investigation relates traditional theories on resistance to change to privatization of the Romanian economy. The authors identified several “inhibitors” which have served to stall Romania’s attempts to achieve a free-market economy. While a lack of practical training in western-style management practices may be a limiting factor, Romanian managers are generally open to change. However, they are still deeply rooted in the thought processes instilled during Romania’s command economy and a belief that the size and economic importance of their firms will serve as buffers against the “agents of change”. To the extent that change is viewed as a threat to their personal interests, resistance can be expected. The question, “what is in it for me?”, must be satisfactorily addressed if Romanian managers are expected to become active partners in implementing necessary changes. © 1999, Nomos Verlagsgesellschaft mbH und Co. All rights reserved.
6 citations (Crossref) [2023-10-31]
Keywords: dept.mgt

Industrial espionage: The dark side of the "Digital Age" - Nodoushani, O.; Nodoushani, P.A. (Competitiveness Review, 2002)
Amid all enthusiasm regarding the rise of the Digital Age, industrial espionage remains the dark side of the post-industrial revolution. The Federal Industrial Espionage Act of 1996 aimed at leveling the field regarding widespread cheating and stealing of intellectual properties by competitors in the marketplace. In this paper we aim at defining various forms of industrial espionage in the light of the ongoing information technology revolution. © Emerald Backfiles 2007.
4 citations (Crossref) [2023-10-31]
Keywords: dept.mgt

Past journeys: Global lessons learned from entrepreneurial women in US history - Oppedisano, J. (International Handbook of Women and Small Business Entrepreneurship, 2005)
Journal Abbreviation: Intern. Handb. of Women and Small Bus. Entrepreneurship
Keywords: dept.mgt

Take charge: Understand control charts and know the difference in variation to better manage your people - Stepanovich, P.L.; Hopkins, P.J. (Quality Progress, 2013)
Keywords: dept.mgt; ⛔ No DOI found

The Effect of Higher Education on Youth Unemployment in European Regions During a Period of Economic Instability - Hermannsson, K.; Scandurra, R.; Graziano, M. (Journal of Education Finance, 2020)
This paper examines the impact of higher education on youth unemployment. Following the 2008 financial crisis, youth unemployment returned to the fore as a serious concern among policy makers in Europe. A crucial difference from previous recessions is that this time around supply of higher education opportunities was much higher than in the 1980s, and indeed higher education participation rates grew rapidly in many regions during this period. Drawing on previous work on youth unemployment and the economic impacts of education we identify a variety of channels through which higher education is likely to influence youth unemployment. We examine this issue using a macro-panel of European regions for the period 2002-2012. This decade was characterized by variation in economic activity and higher education rates. Our results suggest that expansion of higher education during this period had a mitigating effect on youth unemployment and not recognizing this external benefit of education risks underestimating the effects of macroeconomic shocks on young people. © 2020, University of Illinois Press. All rights reserved.
Keywords: dept.mgt; peer-reviewed; ⛔ No DOI found

Participant carelessness: Is it a substantial problem with survey data? - Marasi, S.; Wall, A.; Brewer, K. (Electronic Journal of Business Research Methods, 2019)
For decades, participant carelessness has been considered a problem in collecting data using surveys. Although participant carelessness cannot be disputed to exist, the impact it has on data quality or the level of influence or bias it produces in results is questionable. The main purpose of this paper is to determine whether participant carelessness is a substantial problem that significantly influences or biases the results of statistical analyses. This is accomplished by analyzing established management relationships through a comparison of the full, careful, and careless samples to determine the impact participant carelessness has on data results regarding correlations, t-tests, and simple linear regressions. Four detection approaches were used to identify careless participants individually, in pairs, and in three method combinations. The second purpose of this paper is to use the resampled individual reliability (RIR) approach to detect careless participants and compare it to the individual reliability approach to determine whether the two approaches are fundamentally similar. Data were collected using Mechanical Turk (N = 678). Based on the findings, participant carelessness does not appear to be a substantial problem or demonstrate levels of bias in the results in this study. There are two significant differences between the full and careful samples with the t-tests and the regression comparisons of fit statistics demonstrate the careful samples to have a weak improvement over the full sample however, none indicate bias. The findings also suggest that the individual reliability and the RIR approaches are not entirely fundamentally similar. © ACPIL.
Keywords: Careless responding; Insufficient effort responding; Participant carelessness; Random responding; dept.mgt; peer-reviewed; ⛔ No DOI found

Effect of a brief social contact video on transphobia and depression-related stigma among adolescents: A randomized clinical trial - Amsalem, D.; Halloran, J.; Penque, B.; Celentano, J.; Martin, A. (JAMA Network Open, 2022)
Importance: Transphobia and stigma remain barriers to seeking mental health care for gender-diverse adolescents. Objective: To examine the utility of brief social contact-based video interventions of transgender protagonists with depression to reduce transphobia and depression-related stigma and increase treatment-seeking intentions among adolescents in the general population. Design, Setting, and Participants: During August 2021, a total of 1437 participants were recruited and randomly assigned to 1 of 4 video-based conditions in a 2:2:1:1 ratio: (1) transgender adolescent girls, (2) transgender adolescent boys, (3) cisgender adolescent girls, or (4) cisgender adolescent boys. Interventions: In each of the approximately 110-second videos, an empowered presenter shared their personal story about coping with depression and reaching out for help. Main Outcomes and Measures: The primary outcome was the score on the Attitudes Toward Transgender Men and Women (ATTMW) scale. Secondary outcomes were (1) a "gender thermometer" rating for warmth in transgender perception, (2) the Depression Stigma Scale (DSS) score, and (3) the General Health-Seeking Questionnaire (GHSQ) score. Results: Of the 1437 randomized participants, 1098 (76%) completed the postintervention assessment and passed all the validity tests (mean [SD] age, 16.9 [1.2] years; 481 [44%] male; 640 [58%] White). A significant change in attitudes toward transgender youth was found within the intervention group only (mean [SD] ATTMW scores: intervention group, 34.6 [23.1] at baseline to 32.8 [24.2] after intervention; P ¡.001; control group, 33.5 [23.4] at baseline to 32.4 [24.1] after intervention; P =.01). The mean (SD) total DSS scores decreased significantly across study groups (intervention: 1.3 [3.3]; control: 1.7 [3.3]; P ¡.001). A significant increase in intention to seek help from a parent was found in the intervention (mean [SD] GHSQ score, 0.2 [1.1]) and control (mean [SD] GHSQ score, 0.3 [1.2]) groups (P ¡.001), as was a decrease in those not wanting to seek help from anyone (mean [SD] GHSQ score: intervention, 0.2 [1.6], P =.009; control, 0.3 [1.2], P ¡.001) Secondary analyses revealed significant differences in baseline ATTMW scores and intervention effects between transgender and gender-diverse and cisgender participants and between lesbian, gay, bisexual, or queer (LGBQ) and straight participants (F = 36.7, P ¡.001) and heterosexual participants (F = 37.0, P ¡.001). A significant difference was also found in mean (SD) transgender warmth scores from baseline to after intervention between groups (2.6° [13.1°] in the intervention group vs 0.4° [8.3°] in the control group; P ¡.001). Conclusions and Relevance: In this randomized clinical trial, brief social contact-based videos proved efficacious in reducing transphobia and depression-related stigma and in increasing treatment-seeking intentions among adolescents in the general population. By personifying, individualizing, and providing face and voice to the experience of transgender youth, other adolescents, especially those who are cisgender and/or of a heterosexual orientation, can gain empathetic insights into the lives of their often marginalized and stigmatized fellow youth. Trial Registration: ClinicalTrials.gov Identifier: NCT04969003. © 2022 Collabra: Psychology. All rights reserved.
10 citations (Crossref) [2023-10-31] tex.art_number: e220376 tex.document_type: Article tex.pubmed_id: 35212749 tex.source: Scopus
Keywords: Adolescent; Depression; Female; Humans; Male; Patient Acceptance of Health Care; Prejudice; Social Stigma; Transgender Persons; Video Recording; adolescent; controlled study; depression; dept.mft; dept.swk; female; human; male; patient attitude; peer-reviewed; prejudice; psychology; randomized controlled trial; social stigma; transgender; videorecording

The US Blue New Deal: What does it mean for just transitions, sustainability, and resilience of the blue economy? - Axon, S.; Bertana, A.; Graziano, M.; Cross, E.; Smith, A.; Axon, K.; Wakefield, A. (Geographical Journal, 2022)
The ocean and coasts are largely absent from the “Green New Deal” proposal. In response to the limited attention paid to the sustainability and equitable governance approaches of the blue economy, a US “Blue New Deal” has been proposed aiming to protect the health of the ocean and support coastal communities' adaptation to climate change. The Blue New Deal emerged as a central policy proposal from 2020 Democratic presidential candidate Elizabeth Warren to enhance the role of the blue economy while simultaneously addressing the climate crisis. Through a just transitions analysis, this article evaluates the proposal for a US Blue New Deal — as designed by Senator Elizabeth Warren — that would be applied towards enhancing socioeconomic resiliency, environmental justice, and addressing social inequities. As part of a critical policy analysis evaluating the areas of focus Warren's Blue New Deal presents, environmental justice and sustainability are central to the success of managing, and enhancing the role of, the blue economy. The challenges facing the Blue New Deal reflect a “one size fits all” federal approach that has implications for addressing multifaceted obstacles in key sectors of the blue economy, its governance, and tackling interconnected crises that exacerbate socioeconomic inequities and vulnerabilities of marginalised coastal communities. This article proposes a blue justice framework for the Blue New Deal that seeks to address the tensions and contradictions that exist in its current form and indicates how a comprehensive policy framework can enhance the sustainability and equitable involvement of the blue economy. The information, practices and views in this article are those of the author(s) and do not necessarily reflect the opinion of the Royal Geographical Society (with IBG). © 2022 Royal Geographical Society (with the Institute of British Geographers).
3 citations (Crossref) [2023-10-31] tex.coden: GGJOA tex.document_type: Article tex.source: Scopus
Keywords: dept.egm; dept.mgt; dept.soc; peer-reviewed

Manipulating common method variance via experimental conditions - Wall, A.E.; Simmering, M.J.; Fuller, C.M.; Waterwall, B. (Electronic Journal of Business Research Methods, 2022)
Research data collected from single respondents may raise concerns regarding common method variance (CMV), which is believed to threaten the validity of findings. The primary concern is that CMV can inflate substantive relationships, such that they appear statistically significant when they are not. Thus, understanding the nature of CMV is critical, especially when one considers the popularity—and sometimes necessity—of using self-report data. Research examining CMV has found conflicting evidence about the impact of CMV. Researchers who believe CMV influences findings have proposed solutions to combat any real or perceived potential bias, including changing survey instructions and using marker variables, but few studies have examined the efficacy of these approaches. The purpose of this study is to examine the impact of these techniques and the nature of CMV using an experimental design. To conduct the experiment, multiple versions of a survey, which vary in their use of the remedial approaches, are utilized to collect data, which resulted in 1,069 usable responses. The experimental design was based on the faking literature and included instructions intended to induce or reduce the levels of CMV. Further, two different marker variables are used to determine the degree to which they create a psychological separation in substantive variables. Correlation analysis and measurement invariance are used to analyze the data. This study posits that, if CMV is a substantial concern for self-report data and these approaches are effective, then findings will differ in surveys that incorporate such approaches from surveys that do not. Results indicate few differences in experimental conditions, meaning that regardless of instructions or marker variable, substantive item correlations remained statistically similar. The results indicate this is likely due to the minimal impact of CMV, given that the proposed methods of correction did not significantly influence research findings. These findings have implications for researchers in that they do not support that CMV, or at least its proposed remedies, significantly alter findings. However, support for the null conclusions, in spite of appropriate statistical power, warrant future research examining the nature and impact of CMV. © 2022,lectronic Journal of Business Research Methods. All Rights Reserved.
1 citations (Crossref) [2023-10-31] tex.author_keywords: Common method variance; Experiment; Marker variable; Psychological separation; Same source research tex.document_type: Article tex.source: Scopus
Keywords: dept.mgt; peer-reviewed

The Detrimental Effects of Ethical Incongruence in Teams: An Interactionist Perspective of Ethical Fit on Relationship Conflict and Information Sharing - Shin, Natalie J.; Ziegert, Jonathan C.; Muethel, Miriam (Journal of Business Ethics, 2021)
Building from an interactionist view of ethics, this study sought to integrate individual and contextual factors for understanding ethical perceptions in teams. Given the proximal nature of team members, this study specifically explored how individuals comparatively evaluate their own ethical behaviors and team members’ ethical behaviors to arrive at a perception of ethical person–group (P–G) fit within a team. Grounding our theoretical arguments in relational schemas theory (Baldwin, Psychological Bulletin 112:461–484, 1992), we demonstrate that interpersonal ethical perceptions can have distal impacts on perceptions of team functioning. The results support the hypotheses that a perceived ethical incongruence between the self and other team members (i.e., lack of ethical P–G fit) negatively influenced perceptions of relationship conflict and ultimately information sharing. By exploring individual and team level aspects of ethics concurrently, we contribute to a deeper understanding of contextual forces in ethics through an interactionist approach.
1 citations (Crossref) [2023-10-31]
Keywords: dept.mgt; peer-reviewed

Using contemplative photography in transformative sustainability management education: Pedagogical applications in the united states, russia and germany - Yang, Charlie; Ivanova, Ekaterina; Hufnagel, Julia (The International Journal of Management Education, 2021)
Developing a sustainability mindset requires a transdisciplinary approach to business education that integrates a rational-analytic mode of thinking and an emotive-holistic understanding of the human mind. In order to cultivate the sustainability mindset of business students, we have designed a contemplative art-based project involving the creation of an electronic portfolio which consists of a student's digital photographs. We have integrated it into our teaching of management courses in the United States, Russia, and Germany, respectively. The project aims to enable business students to become more visually attentive and environmentally conscious, so that they will pay close attention to the process of building more sustainable relationships within their natural and social environments. From the interpretative phenomenological perspective, we have analyzed the students' e-portfolios in order to understand how business students make sense of environmental and human sustainability. While envisioning more transformative sustainability management education, we have also discussed the pedagogical implications of making the e-portfolios for enhancing the students' understanding of the sustainability mindset. © 2021 Elsevier Ltd
3 citations (Crossref) [2023-10-31] https://publications.hse.ru/articles/523564895
Keywords: dept.mgt; peer-reviewed

Socio-economic impacts of the Great Lakes restoration initiative - Liesch, Matthew; Graziano, Marcello (Geographical Review, 2021)
Interviews illuminate impacts of the Great Lakes Restoration Initiative (GLRI), a United States’ federal program designed to improve the Great Lakes by restoring the region’s most polluted harbors and coastal landscapes. To see how GLRI funds caused changes in the built environment and to attitudes toward place, semi-structured interviews were conducted with private- and public-sector leaders. Case studies are four EPA-designated Areas of Concern receiving substantial GLRI funds in Buffalo, New York; Duluth-Superior, Minnesota and Wisconsin; Muskegon, Michigan, and Sheboygan, Wisconsin. Results show that GLRI serves as a catalyst in three principal ways: The program leveraged local and state funds, both private and public. GLRI also leads to greater socio-spatial consciousness regarding rehabilitated places. Also, GLRI had led to stronger and deeper senses of place. This study reveals interviews help to calculate a more holistic return on investment for a prominent federal program. This study offers a way forward for ecosystem services research to take a more holistic view than has traditionally been done, in that semi-structured interviews illuminate impacts that traditional economic modeling alone cannot. Concurrently, this research is an example of how a prominent federal program affects community perceptions integral to holistic coastal planning processes. © Copyright © 2021 by the American Geographical Society of New York.
3 citations (Crossref) [2023-10-31]
Keywords: dept.mgt; peer-reviewed

Validity and reliability of the lode excalibur sport cycle ergometer for the wingate anaerobic test. - Lunn, William R.; Axtell, Robert S. (Journal of strength and conditioning research, 2021)
https://europepmc.org/article/MED/31453946 ; https://pubmed.ncbi.nlm.nih.gov/31453946/ ; https://dialnet.unirioja.es/servlet/articulo?codigo=8169588
Keywords: dept.mgt; peer-reviewed; ⛔ No DOI found

Environmental performance, environmental management and company valuation - Abrams, Roy; Han, Seungmin; Tanzeeb Hossain, Mehdi (Journal of Global Responsibility, 2021)
Purpose: This paper aims to investigate the relationship between environmental performance and management and company valuation. With a specific focus on company valuation, this study shows how a firm’s environmental activities, including its environmental management practices, are perceived and valued by its stockholders. Design/methodology/approach: Newsweek’s green ranking data between 2014 and 2016 were used to support this analysis. Environmental performances and environmental management practices of 345 Fortune 500 companies from various industries were included in the data set. Findings: The analysis finds higher valuations for US companies that are more efficient in managing greenhouse gas emissions. In addition, it empirically shows that investors place a higher value on companies with the following environment-related management policies: initiatives that reward top management for achieving environmental goals and third-party auditing of environmental performance. Originality/value: By incorporating corporate environmental management practices as an additional environmental performance criterion, this research fills a gap in the literature on the potential relationship between corporate environmental performance and company valuation. © 2021, Emerald Publishing Limited.
6 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85118117232
Keywords: dept.mgt; peer-reviewed

Legacy and shockwaves: A spatial analysis of strengthening resilience of the power grid in Connecticut - Gallaher, Adam; Graziano, Marcello; Fiaschetti, Maurizio (Energy Policy, 2021)
Grid resilience and reliability are pivotal in the transition to low and zero carbon energy systems. Tree-trimming operations (TTOs) have become a pivotal tool for increasing the resilience power grids, especially in highly forested regions. Building on recent literature, we aim at assessing the temporal and spatial extents of the benefits that TTOs produce on the grid from three perspectives: the frequency, extent, and duration of outages. We use a unique dataset provided by Eversource Energy, New England's largest utility company, with outage events from 2009 to 2015. We employ spatial econometrics to investigate both the legacy and spatial extent of TTOs. Our results show TTOs benefits occur for all three metrics for at least 4 years, and benefits spillover to up to 2 km throughout the treated areas, with significant spatial spillovers across the state greater than direct effects. Implications lead to supporting TTOs as part of the hardening policies for utility companies, especially as home-based activities increase in importance in a post-COVID19 world. © 2021 Elsevier Ltd
12 citations (Crossref) [2023-10-31] https://discovery.ucl.ac.uk/id/eprint/10138230/ ; https://www.sciencedirect.com/science/article/pii/S0301421521004523
Keywords: COVID-19; Connecticut; Economics; Electric power transmission networks; Energy transitions; Low carbon; Outages; Power grids; Spatial analysis; Spatial extent; Spatial modelling; Statistics; Tree trimmings; Trimming; Trimming operations; United States; Utilities companies; Vegetation management; atmospheric electricity; data set; dept.mgt; econometrics; electricity; smart grid; spatiotemporal analysis; utility sector

Integrating returns and costs in examining faster firm speed - Lee, Minjae (Academy of Management Proceedings, 2021)
0 citations (Crossref) [2023-10-31]
Keywords: dept.mgt

A data-based approach to identifying regional typologies and exemplars across the urban–rural gradient in Europe using affinity propagation - Fiaschetti, Maurizio; Graziano, Marcello; Heumann, Benjamin W. (Regional Studies, 2021)
We apply recent developments in data-mining and statistics, using affinity propagation (AP) to identify regional typologies in the European Union (EU) and characterize major factors between rural–rural and rural–urban regional differences, without predetermined thresholds. We identify a representative ‘exemplar’ within each cluster using the drivers of Copus enriched with climate and land-cover/land-use variables to provide geographical context and pinpoint differences driven by natural and human–natural landscapes. Building upon the works of Dijkstra and the Eudora Project, we expand the dimensions of regional differences, introducing a threshold-less, data-driven model able to identify exemplars, and the main characteristics of each cluster or regional typology. © 2021 Regional Studies Association.
5 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85100769962
Keywords: Europe; European Union; data mining; dept.mgt; economic development; peer-reviewed; regional development; urban-rural migration

A comparison of two multilingual meeting systems - Aiken, Milam; Park, Mina (International Journal of Computers & Technology, 2020)
0 citations (Crossref) [2023-10-31]
Keywords: Google Translate; dept.bis; dept.mgt; peer-reviewed

Increasing demand and a tradeoff between speed-cost efficiencies and total profits - Lee, Minjae (Academy of Management Proceedings, 2020)
0 citations (Crossref) [2023-10-31]
Keywords: dept.mgt

Developing the elusive construct of speed-cost efficiency - Lee, Minjae; Mahoney, Joseph T. (Academy of Management Proceedings, 2020)
0 citations (Crossref) [2023-10-31]
Keywords: dept.mgt

A temporal analysis of employees’ situational work motivation and well- being - Wang, Zheni; Panaccio, Alexandra Joelle (Academy of Management Proceedings, 2020)
0 citations (Crossref) [2023-10-31]
Keywords: dept.mgt

Business students' perceptions of women in management - Frank, Ellen J (Sex Roles, 1988)
This study surveyed 202 undergraduate business majors regarding their perceptions of women in management. Research focused on male and female students' acceptance of women managers, the extent students perceived women managers as being accepted by others, and a comparison of descriptions of the typical male and female manager. Male students were found to be less accepting of women's dual role. Men perceived women managers as being less knowledgeable and possessing poorer managerial skills than male managers. Women managers were perceived as having greater interpersonal skills. Female students showed a greater preference for a male boss. Their descriptions of women managers were more positive regarding competency, but emphasized an interpersonal rather than a task orientation. The conclusion is made that perceptual stereotypes have not radically changed when compared to research reported in the 1970s. © 1988 Plenum Publishing Corporation.
26 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/052-483-800-573-559 tex.type: [object Object]
Keywords: dept.mgt

Designing and implementing a personnel mis - Frank, EJ (Personnel, 1987)
tex.unique-id: ISI:A1987K654900011
Keywords: dept.mgt; ⛔ No DOI found

Noren discount stores: death of a family business - Goldberg, Steven D (Family Business Review, 1997)
This case is about a family-owned discount store chain that was unable to survive much beyond its founder. It tells the story of a first-generation American family and its struggle to grow and prosper in a family business during the early 1900s. The case takes the reader through the business' growth, maturity, decline, and, ultimately, its demise in 1991, which was brought about by issues such as organizational structure, the role of family in the family business, lack of succession planning, and myopic strategic planning. The author uses fictitious names, dates, and places to protect the surviving family members' privacy, and to ensure confidentiality.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/091-132-571-002-970 tex.type: [object Object]
Keywords: dept.mgt

Organizational cynicism - Dean, James W.; Brandes, Pamela; Dharwadkar, Ravi (Academy of Management Review, 1998)
448 citations (Crossref) [2023-10-31]
Keywords: dept.mgt

Give your work teams time and training - Cottrill, Melville (Academy of Management Perspectives, 1997)
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/081-609-007-389-847 tex.type: [object Object]
Keywords: dept.mgt

Predicting corporate social responsiveness: A model drawn from three perspectives - Beliveau, Barbara; Cottrill, Melville; O'Neill, Hugh M. (Journal of Business Ethics, 1994)
Most studies of corporate social responsiveness (CSR) focus on the relationship between CSR and profit. Here, we use three perspectives (institutional theory, economic theory and agency theory) to explain CSR. Industry norms, market share and indicators of management reputation predict variance in CSR. The combined perspectives improve understanding of both CSR and the CSR-profit relationship in two ways. First, they suggest that CSR levels and their relationship with profit will vary by industry. Second, they suggest that stock market measures and accounting measures will respond differently to CSR measures. Stock market measures lead, while accounting measures lag, CSR.
59 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1994PE94100010 tex.unique-id: [object Object]
Keywords: Agency Theory; Economic Growth; Economic Theory; Market Share; Stock Market; dept.mgt

Using simulations to investigate management decision making - Prohaska, Charles R; Frank, Ellen J (Simulation & Gaming, 1990)
Management researchers are always in search for new controlled environments from which they can gather data. This article proposes the use of total enterprise simulations as a research setting for studying management decision making. Using INTOP, the authors present examples of analyses that were conducted from a data base generated from the responses of executive MBA participants. Using a multiple regression, policy-capture approach, differences in the decision making strategies between groups are examined. Also discussed is an approach to developing a performance criterion that may be used when testing hypotheses regarding managerial decision-making effectiveness. The authorsconclude that total enterprise simulations represent a research setting that warrants further exploration. © 1990, SAGE Publications. All rights reserved.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/037-367-418-569-979 tex.type: [object Object]
Keywords: decision making; dept.mgt; management performance; policy capture; research methodology; simulation

Chatbots for Multilingual Conversations - Vanjani, Mahesh; Aiken, Milam; Park, Mina (Journal of Management Science and Business Intelligence, 2019)
Chatbots emulate human dialogue to provide a more intuitive user interface to applications or simply provide entertainment. Chatbots rely on technology to function and new and emerging technologies such as NLP (Natural Language Processing) and AI (Artificial Intelligence) can be used to increase the ability of chatbots to emulate a more natural and free flowing conversation. As more and more mobile device users transition to increased use of texts and messaging chatbots can be used to provide consumers with multilingual support and services. While some chatbots have been developed in other languages, currently most converse only in English, and only a few can communicate in multiple languages. If configured correctly multilingual chatbots have the potential of providing a digital communication option that transcends language barriers. For our research we focused on the use of a chatbot that links the English-speaking Tutor Mike system with Google Translate, thus providing conversational capability in 103 languages, which is more than any other artificial multilingual agent is currently capable of. Two humans communicated with the system using German, Spanish, and Korean, and a group of undergraduate students reviewed the English translations of the chatbot’s replies. Results show that the responses from German and Spanish were cogent and natural, but those from Korean were less understandable. As a caveat, Asian languages lack much of the linguistic nuances of European languages. For example, there may be no plural form or gender in the Asian language. Unlike German where nouns and adjectives constantly change endings depending on what they are doing in a sentence and, unlike Spanish, which have numerous verb conjugations, Asian languages require no such changes. This might impact the translation ability and quality of a multilingual chatbot. Additional research and enhancements can improve chatbots used for European to Asian language translations and vice-versa. Regardless, our research shows promising results in the future use of multilingual chatbots to allow communication across the globe with business potential in the use of such chatbots to provide customer service and online live interaction with customers across the world.
Keywords: Chatbot; Multilingual; Communication; Machine Translation; dept.bis; dept.mgt; peer-reviewed

Learning practices: Assessment and action for organizational improvement - Hopkins, Pamela J (Academy of Management Learning and Education, 2005)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/074-546-699-807-413 tex.type: [object Object]
Keywords: dept.mgt

Using system dynamics to illustrate deming’s system of profound knowledge - Stepanovich, Paul L (Total Quality Management & Business Excellence, 2004)
This article presents a systems dynamics model to illustrate some of the aspects of Deming's System of Profound Knowledge. As a pedagogical tool, it would serve as a useful introduction for those new to Deming's ideas. It not only introduces the main parts of his system, but also highlights their interconnectedness. The model environment, an interactive management flight simulator, and the model content combine to provide several learning opportunities. The model uses the assumptions of regression to the mean, the 80:20 Rule, random walks, and learned helplessness to present a theory of how, managers learn to reduce quality in organizations. Those interested in exploring or teaching Deming's System can use the model as a launching point from which to explore the system further. Running the simulation provides an opportunity to identify and challenge assumptions, explore the harmful effects of tampering, examine the fundamental attribution error, develop control charts, and challenge the application of behaviourism in management.
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/024-680-699-761-383 tex.type: [object Object]
Keywords: Deming; Pedagogy; Quality; System dynamics; dept.mgt

Process mapping in successful ERP implementations - Okrent, Michael D; Vokurka, Robert J (Industrial Management and Data Systems, 2004)
This paper discusses the six core business processes and supporting technology that are impacted by an enterprise resource planning (ERP) implementation. It begins with a brief history of the evolution of ERP and the information systems technology that enabled its development. A discussion of project implementation team preparations is followed by a description of process mapping and its significance to the success of an ERP implementation. Highlights of “As-Is” and “To-Be” process mapping and change management conclude the paper. © 2004, Emerald Group Publishing Limited
69 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/020-734-989-711-339 tex.type: [object Object]
Keywords: Business processes; Costs; Enterprise resource planning; Information analysis; Information technology; Maintenance; Optimization; Planning tools; Process analysis; Process mapping; Resource management; Strategic planning; dept.mgt

Giving back: women's entrepreneurial philanthropy - Oppedisano, Jeannette (Women in Management Review, 2004)
Traditionally, the concept of entrepreneurship included a for-profit bottom line. Recently, however, researchers have begun to explore an adaptation of this model called “social entrepreneurship”; that is, creating organizations for the greater good of a community, region, nation, or the world. These entrepreneurs use money that they made or inherited to establish organizations from a missionary and visionary posture. This is an arena where women have had significant impact, yet little has been written to celebrate their contributions. The purpose of this paper is to explore the concept of such philanthropy, to suggest where this social ethic might have had its origins, and to provide samples of women who have been entrepreneurial in their social commitment. Suggestions for future research on women's entrepreneurial philanthropy will also be made. © 2004, Emerald Group Publishing Limited
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/020-771-605-085-74X tex.type: [object Object]
Keywords: Entrepreneurialism; Philanthropy; Social action; United States of America; Women; dept.mgt

Leadership theory and practice: a “case” in point - Armandi, Barry; Oppedisano, Jeannette; Sherman, Herbert (Management Decision, 2003)
Leadership theory has little value if it cannot be applied to real world situations. A summary review of the literature on leadership theory is provided here first. A disguised real case concerning Ted Shade, a Vice-President at Galactic Chips, Inc. is then provided which describes a manager who is extremely task-oriented. The case analysis follows. It includes questions and answers which connect leadership theory to case specifics and requires learners to analyze the case using differing leadership models. © 2003, MCB UP Limited
26 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/066-531-695-412-316 tex.type: [object Object]
Keywords: Leaders; Leadership; Management styles; Psychology; dept.mgt

Vitality alliance: adventures in entrepreneurial consulting - Page, Robert A (The international journal of entrepreneurship and innovation, 2003)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/081-033-379-669-736 tex.type: [object Object]
Keywords: dept.mgt

The strategic management of research and development - Nodoushani, Omid; Nodoushani, Patricia A (Journal of Comparative International Management, 2002)
Citation Key Alias: lens.org/051-498-885-514-43X tex.type: [object Object]
Keywords: dept.mgt; ⛔ No DOI found

Book Review: Resource ReviewsTaking center stage: masterful public speaking using acting skills you never knew you had, by GottesmanDeb and MauroBuzz. new york, NY: berkley books, 2001. 191 pages, soft cover. - Oppedisano, Jeannette (Academy of Management Learning and Education, 2002)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/127-128-939-707-091 tex.type: [object Object]
Keywords: book.review; dept.mgt

Chinese students’ perceptions of women in management: will it be easier? - Frank, Ellen J (Women in Management Review, 2001)
An attitude survey was conducted with 72 management majors attending a prestigious business university in Beijing, China. The results indicate that there is still a significant “glass ceiling” effect to accepting women as they climb up the management hierarchy. The group estimated that it would take at least 32 years before equality would be reached. Women were less likely to prefer to work for a woman than for male subjects. Women were described as more incompetent, slower, weaker, more a follower-than-a-leader, more lenient, more democratic, less active, and more friendly than male managers. Women were significantly more in agreement with the idea of being both a professional and a wife. The results reflect a similar attitudinal position to US women. The conclusion is that it will not be easier for Chinese women to succeed than it is for women in theUSA. © 2001, MCB UP Limited
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/077-606-789-075-245 tex.type: [object Object]
Keywords: Attitudes; China; Management; Managers; Perception; Women; dept.mgt

A postmodern theory of industrial democracy - Nodoushani, Omid; Nodoushani, Patricia A (Journal of Comparative International Management, 2000)
Citation Key Alias: lens.org/172-802-474-366-920 tex.type: [object Object]
Keywords: dept.mgt; ⛔ No DOI found

The lobster tale: an exercise in critical thinking. - Stepanovich, Paul L (Journal of Management Education, 2009)
Professors in management and business are encouraged to incorporate critical thinking as an objective in their courses. "The Lobster Tale" provides an opportunity to engage students in various levels of critical thinking, ranging from a relatively superficial reading to an examination of the deeper, often hidden issues. Using the foundations of critical theory and systems theory, the story draws on economics, social theory, philosophy, and other disciplines to present a simplified version of the complexities found in our global environment. It can be used to supplement a variety of courses in the business curriculum and to encourage students to challenge not only assumptions but also conventional wisdom and, perhaps, knowledge itself. © 2009 The Author(s).
10 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/035-736-247-110-079 tex.type: [object Object]
Keywords: Affirmative action; Critical theory; Critical thinking; Systems theory; Tragedy of the commons; dept.mgt

The concept of implementing effective learning assessment criteria in a virtual environment - Goralski, Margaret A (Estableciendo puentes en una economía global, Vol. 1, 2008 (Ponencias), ISBN 978-84-7356-556-1, pág. 39, 2008)
Citation Key Alias: lens.org/040-937-411-377-317
Keywords: dept.mgt; ⛔ No DOI found

Aligning health care: quality as a learning system - Goralski, Margaret A; Page, Robert A (Estableciendo puentes en una economía global, Vol. 1, 2008 (Ponencias), ISBN 978-84-7356-556-1, pág. 36, 2008)
Citation Key Alias: lens.org/037-680-207-604-077
Keywords: dept.mgt; ⛔ No DOI found

40 years of academic public psychiatry - ethnicity, mental health care disparities and culturally competent care at the connecticut mental health center - Nazroo, James; Blue, Howard C.; Añez, Luis M.; Paris, Manuel; Hawkins, Dietra; Page, Robert A. (John Wiley & Sons, Ltd, 2007)
Keywords: dept.mgt

Ethnicity, mental health care disparities and culturally competent care at the connecticut mental health center - Nazroo, James; Blue, Howard C; Anez, Luis M; Paris, Manuel; Hawkins, Dietra; Page, Robert A (40 Years of Academic Public Psychiatry, 2007)
Keywords: Community-based prevention efforts; Deinstitutionalization impact; Housing and employment discrimination; Psychotic disorders and unrelenting affective disorders; Third psychiatric revolution; dept.mgt

Role modeling as a pedagogical strategy in entrepreneurship education for women and girls: An interactive model of transformational learning - Oppedisano, Jeannette; Laird, Kenneth R (New England Journal of Entrepreneurship, 2006)
This article presents a pedagogical model that utilizes students as primary researchers in the identification, interviewing, and then reporting on women entrepreneurs as a major component of a multidisciplinary entrepreneurship course. The purpose of the course is to attract students who may not be familiar with the entrepreneurship concept itself, the role of women in such economic ventures, or the possibilities for people like themselves in such a career avenue. Students are exposed to the accomplishments of women entrepreneurs throughout U.S. history in the broad categories of agriculture and mining; construction; communication; manufacturing; service (both for profit and not-for-profit); transportation; and wholesale and retail trade. This content experience is then enhanced by the studentsʼ own direct interaction with and interviewing of women entrepreneurs. The implementation, potential outcomes, and possible adaptations of the course are described, and this transformational learning process model is illustrated. © Published by DigitalCommons©SHU, 2006.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/112-478-351-659-477 tex.type: [object Object]
Keywords: dept.mgt

Thinkubator Approach to Solving the Soft Skills Gap - Stewart, Carol; Marciniec, Sheryl; Lawrence, Denval; Joyner-McGraw, Laquita (American Journal of Management, 2020)
0 citations (Crossref) [2023-10-31]
Keywords: dept.mgt; peer-reviewed

A Self-Determination Approach to Understanding Individual Values as an Interaction Condition on Employees' Innovative Work Behavior in the High-Tech Industry - Wang, Zheni; Gao, Mengchan; Panaccio, Alexandra (Journal of Creative Behavior, 2021)
Drawing on self-determination theory (SDT; E.L. Deci & R.M. Ryan, 1985, 2000) and using corporate samples (N = 284; 63% Male; Mean Age = 34, SD = 6.09) from high-tech firms in China, this empirical study explored the path model from satisfaction of the basic psychological needs for autonomy, competence, and relatedness, through autonomous motivation to employees' innovative work behavior (“IWB”; J. De Jong & D. Den Hartog, 2010). It also simultaneously examined the interactions between autonomous work motivation and individual values (collectivism, H.C. Triandis (1995); uncertainty avoidance, R. J. House, P. J. Hanges, M. Javidan, P. W. Dorfman, & V. Gupta (2004); and power distance, J. Farh, R.D. Hackett, & J. Liang (2007)) in the conditioned path model. The regression results obtained from conditional PROCESS analysis (A.F. Hayes, 2013, 2018) suggest that basic psychological needs satisfaction is positively related to employees' IWB via autonomous motivation, but that these indirect effects were weaker when employees' power distance value orientation was high. Implications, limitations, and future research directions are discussed. © 2020 by the Creative Education Foundation, Inc.
14 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85082766274
Keywords: dept.mgt; peer-reviewed

The green MBA: a competing values matrix - Page, Robert A; Collins, Kirsten A (Competitiveness Review: An International Business Journal Incorporating Journal of Global Competitiveness, 2010)
Purpose – The purpose of this paper is to review and categorize the different strategies Master of Business Administration (MBA) programs have adopted towards incorporating environmental sustainability into business administration. Design/methodology/approach – Through extensive internet research looking at colleges and universities, data are collected from primary source web sites and administrative school contacts. There are 35 institutions whose MBA programs address sustainability in some way. Each of these institutions is then organized by location, tuition cost, enrollment, year founded, accreditation, and curriculum. Findings – Green educational strategies differentiate themselves by the size and maturity of the program. Larger, established institutions typically opt for the green major, or a dual degree, and tend to leave systematic integration of sustainability to the individual student. Newer and smaller entrants tend to either dabble in green with a few sustainability courses, or completely embrace and systemically integrate sustainability throughout the program. Research limitations/implications – The sample focuses on US institutions and treats sustainability as an externally validated curricular choice when it may merely be an educational fad. The sample excludes potential green MBA programs that lack a strong internet presence. Practical implications – Four archetypes are identified: dual degree, all-green, green major, and green coursework. Institutions can analyze their performances and see where they fall on the two major continua – integration and maturity/size. Originality/value – Green MBA programs are relatively new on the academic landscape, and this research paper is one of the first to systematically analyze and categorize them. © Emerald Group Publishing Limited.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/062-866-418-386-446 tex.type: [object Object]
Keywords: Curricula; Economic sustainability; Education; Environmental studies; Master of business administration; dept.mgt

AACSB accreditation and possible unintended consequences: A deming view. - Stepanovich, Paul L; Mueller, James; Benson, Dan (The Journal of Education for Business, 2014)
The AACSB accreditation process reflects basic quality principles, providing standards and a process for feedback for continuous improvement. However, implementation can lead to unintended negative consequences. The literature shows that while institutionalism and critical theory have been used as a theoretical base for evaluating accreditation, W. E. Deming's philosophy has not. This article fills that void by examining possible negative consequences in meeting faculty qualification requirements in institutions with a teaching mission. © 2014, Copyright Taylor & Francis Group, LLC.
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/019-359-118-710-616 tex.type: [object Object]
Keywords: AACSB accreditation; Deming; dept.mgt; profound knowledge

Time horizon of investments in the resource allocation process: review and framework for next steps - Reilly, Greg; Souder, David; Ranucci, Rebecca (Journal of Management, 2016)
Corporate investment inherently relies on time horizon, as profits result from acquiring assets or developing capabilities that yield future benefits that exceed upfront costs. Despite the importance of time horizon to understanding resource allocation, knowledge about the subject has accumulated slowly. Our review therefore encompasses insights from several research streams that partially address the subject even though time horizon is not the central construct in any of them. We aim to clarify key constructs related to time horizon, organize prior research about the antecedents of time horizon, explain the implications of several theoretical traditions for time horizon, and detail the range of measures that have been used to capture time horizon empirically. By focusing narrowly on this topic but searching broadly for references, we provide integrative summaries of existing research and identify opportunities for new and unique research.
50 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/002-114-184-051-652 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: behavioral strategy; decision making; dept.mgt; resource allocation/management

Mindfulness meditation and art appreciation as meaning-making practices - Yang, Charlie (Academy of Management Proceedings, 2016)
Mindfulness has recently gained significant attention and momentum in academia and popular culture. There is, however, a paucity of literature on how students make sense of contemplative practices. This paper proposes that mindfulness meditation is not merely a useful tool for stress reduction, but also a metacognitive meaning-making practice.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/021-315-407-614-417
Keywords: Art appreciations; Contemplative practice; Meaning makings; Metacognitives; Popular cultures; Stress reduction; dept.mgt

Gossip in organizations: from an evolutionary psychological perspective - Yang, Chulguen; Minjock, Robert; Voss, Bernard Edward; Colarelli, Stephen M (Academy of Management Proceedings, 2014)
Gossip is often portrayed as a trivial and even destructive behavior at work. This paper integrates previous studies on gossip using a multilevel evolutionary framework and proposes a few empirical propositions to develop a more balanced view on gossip as a medium of informal communication in organizations.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/079-776-281-946-710
Keywords: Evolutionary framework; Informal communication; dept.mgt

Language fluency as a factor in machine translation comprehension - Aiken, Milam; Park, Mina; Lindblom, Tobin (International Conference on Bioinformatics, 2013)
0 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: dept.mgt

Pernicious performance appraisals: A critical exercise - Stepanovich, Paul L (Journal of Behavioral and Applied Management, 2013)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/123-469-061-094-943 tex.type: [object Object]
Keywords: dept.mgt

Telling tales at work: an evolutionary explanation - Yang, Chulguen (Business Communication Quarterly, 2013)
This article explores the adaptive functions of storytelling in the workplace from an evolutionary perspective. Based on the analysis of ethnographic studies on hunter-gatherer and modern work organizations, this article claims that storytelling, as an adapted cognitive device, was selectively retained by natural and sexual selection, because of its survival and reproductive payoff. The narrative production through storytelling is a natural coping mechanism and has been functional in both old and new ways of working life under different ecological conditions. This article also highlights underlying adapted psychological mechanisms of storytelling and discusses some evolutionarily informed practical implications and pedagogical applications. © 2013 by the Association for Business Communication.
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/047-449-660-219-354 tex.type: [object Object]
Keywords: dept.mgt; narrative; oral presentations; organizational communication

Telling tales at work: an evolutionary psychological explanation - Yang, Chulguen (Academy of Management Proceedings, 2012)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/112-288-802-738-354
Keywords: dept.mgt

Start-up and hiring practices of immigrant entrepreneurs: An empirical study from an evolutionary psychological perspective - Yang, Chulguen; Colarelli, Stephen M; Han, Kyunghee; Page, Robert A (International Business Review, 2011)
Strong social ties embedded in ethnic communities of immigrant populations have been considered key assets for immigrant entrepreneurs. However, little research has been done on how biological kinship and the biological theories of altruism influence the behavior of ethnic entrepreneurs. In this study, we have applied a neo-Darwinian evolutionary theory of kinship to examine adaptive functions of kin and ethnic altruism in business start-up and hiring practices of Korean immigrant entrepreneurs in the United States. We confirmed that the patterns of help received by Korean entrepreneurs for business start-ups were congruent with an evolutionary perspective on altruism. However, the results for hiring patterns suggested that customer ethnicity trumped kin and co-ethic interests. We close by offering suggestions for future research. (C) 2011 Elsevier Ltd. All rights reserved.
23 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/092-753-567-946-985 tex.type: [object Object]
Keywords: Ethnic nepotism; Evolutionary psychology; Immigrant entrepreneurship; Inclusive fitness theory; Kin altruism; dept.mgt

Biased against whom? The problems of “Group” definition and membership in test bias analyses - Colarelli, Stephen M; Han, Kyunghee; Yang, Chulguen (Industrial and Organizational Psychology, 2010)
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/094-090-854-033-984 tex.type: [object Object]
Keywords: dept.mgt

Uncovering Relations Between Leadership Perceptions and Motivation Under Different Organizational Contexts: a Multilevel Cross-lagged Analysis - Gagné, Marylène; Morin, Alexandre J. S.; Schabram, Kira; Wang, Zhe Ni; Chemolli, Emanuela; Briand, Mélanie (Journal of Business and Psychology, 2020)
Surprisingly scant research has adequately examined directional influences between different perceptions of managerial leadership behaviors and different types of work motivation, and even fewer studies have examined contextual moderators of these influences. The present study investigated longitudinal and multilevel autoregressive cross-lagged relations between perceptions of transformational, transactional, and passive-avoidant leadership with autonomous motivation, controlled motivation, and amotivation. Multilevel longitudinal models were estimated on data from 788 employees, nested under 108 distinct supervisors, from six Canadian organizations. Results revealed that perceptions of leadership behaviors predicted changes in motivation mostly at the collective level and that some of these relations changed as a function of whether organizations had recently faced a crisis. Collective perceptions of transformational leadership were related to increased collective autonomous and controlled motivation, while individual controlled motivation was related to increased individual perceptions of transactional leadership. In organizations facing a crisis, individual perceptions of transactional leadership were related to decreased individual controlled motivation, while collective perceptions of transactional leadership were related to increased collective autonomous motivation and decreased collective amotivation. In organizations not facing a crisis, collective perceptions of transactional leadership were related to decreased collective autonomous motivation. Implications for theory and practice are discussed.
11 citations (Crossref) [2023-10-31] tex.ids: gagneUncoveringRelationsLeadership2020, lens.org/066-744-892-590-102, pop00060 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85071718155 tex.type: [object Object] type: Article
Keywords: Autonomous motivation; Multilevel modeling; Transactional leadership; Transformational leadership; dept.mgt; peer-reviewed

Should employees be “dooced” for a social media post? The role of social media marketing governance - Parker, Janna M.; Marasi, Shelly; James, Kevin W.; Wall, Alison (Journal of Business Research, 2019)
Instances of employees being `dooced' because of a social media post are becoming commonplace. Three research questions are presented to better understand workplace firings due to social media posts using justice theory and social convergence to fit within the nomological net. The first question examines employees' awareness of their employer's social media policy. The second question examines the role of offensiveness in the perceived fairness of the termination. The third question asks whether work-related posts (social convergence) and the presence of a social media policy (social media governance) influence the perception of termination fairness. Two data collection efforts are presented to test the research questions. The research findings extend the social media marketing governance literature by incorporating role theory and script theory. Managerial implications include the importance of developing and communicating to employees the organization's social media policies.
11 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/064-072-744-556-090, pop00132 tex.type: [object Object]
Keywords: Justice theory; Role theory; Script theory; Social convergence; Social media marketing governance; Termination fairness; dept.mgt; peer-reviewed

Piggy-backing an O.B. experience on the total enterprise simulation - Frank, Ellen J (Journal of Effective Teaching)
Keywords: dept.mgt; peer-reviewed; ⛔ No DOI found

Family Law and Practice - Luppino, Grace A.; Miller, Justine FitzGerald (Pearson, 2020)
For courses in family law for students in paralegal studies programs, broader legal studies programs, and those majoring in criminal justice, social work, and education. Connecting theory, history, and practice in family law Family Law and Practice prepares students to enter the workplace with a firm grasp of family law and procedural components of family law practice. To meet this challenge, the authors have divided the 5th edition into two parts: the first introducing the principles of family law and the second translating theory into practice. The new edition also addresses changing views on marriage, spousal roles, children’s status in the family, and even what constitutes a family. It also adds cases, statutes, and legal forms from a variety of US states to engage students across the country.
Keywords: Domestic relations; Handbooks; manuals; etc; United States; United States; Legal assistants; dept.mgt; faculty_collection

Soft skill development in a total enterprise simulation - Frank, Ellen J (Business Education Innovation Journal, 2019)
Keywords: dept.mgt; peer-reviewed; ⛔ No DOI found

Participant carelessness: Is it a substantial issue in survey research? - Marasi, S.; Wall, A.; Brewer, K. (Electronic Journal of Business Research Methods, 2019)
Keywords: dept.mgt; peer-reviewed; ⛔ No DOI found

Automated translation preference with a bilingual chatbot - Park, Mina; Aiken, Milam (International Journal of Computers & Technology, 2019)
Free, online language translation services are being used by people around to the world to facilitate communication. However, it takes time and effort for a person to load the Web page in a browser, copy and paste text into the site, and translate words. The process quickly becomes tiresome. Instead, some computer programs are providing automated translation. However, no studies have been conducted to determine the efficiency or effectiveness of such an approach. In this study, we compare how students used an English-based chatbot with and without German automatic translation. Results show that students took nearly 1.5 times longer than their stated upper time limit to manually translate. In contrast, the automated translation was at least 30 times faster. In addition, the students were significantly more satisfied with the automated than the manual system.
2 citations (Crossref) [2023-10-31] Citation Key Alias: pop00215 tex.type: [object Object]
Keywords: Chatbots; Google Translate; Tutor Mike; artificial conversation; dept.bis; dept.mgt; machine translation; peer-reviewed

Handbook on household hazardous waste - Cabaniss, Amy (Bernan, 2018)
Household hazardous waste (HHW) is a topic that affects every individual and community given the nearly universal use, storage, and disposal of chemical consumer products. Yet many communities lack the basic information, guidance, and planning support for HHW collection and management so that struggles (e.g., to gain politicians’ and residents’ support, host a collection, build a facility, affect behavior change, and encourage extended producer responsibility) continue on a regular basis. This book is for professionals, students, government officials and others interested in HHW and accommodating the increasing societal demand for this disposal option. In the evolving field of HHW collection and management, this book: provides an unparalleled, comprehensive look at household hazardous wasteis a must-have for anyone interested in the solid waste management field, whether novice or experienced, because of the valuable overview and specifics it provides for addressing the ubiquitous issue of HHWoffers perspectives based on many collective years of experts’ accrued insightthe chapters are written by leading practitioners and visionariesis packed with useful information on many aspects of HHW including its definition, mechanisms for collection and creative collection options, tools for behavior change, and product stewardshipoffers an extensive resource list for more information. Much has changed in 10 years since the first edition appeared, and each chapter in the Handbook on Household Hazardous Waste, Second Edition, is updated to reflect changes and advances in the field of HHW collection and management. This includes updated appendices and the extensive resource list.
Keywords: dept.mgt

Kinship ties and employee theft perceptions in family-owned businesses - O'Brien, Kimberly E; Minjock, Robert; Colarelli, Stephen M; Yang, Chulguen (European Management Journal, 2018)
Family business research typically views family firms using the frameworks developed for non-family businesses (e.g., agency theory, institutional theory). Thus, using an evolutionary perspective on family may help address gaps in the family business literature, particularly regarding deviance. In the current study, we use kin selection theory to predict that family members receive preferential treatment and this history of privileges can create entitlement and lead genetically-related employees to misuse company resources. Using an experimental vignette methodology and data from 161 people recruited from an online panel, we found that the participants' purported genetic relatedness to the owner of a business increased their theft intentions and decreased their expected severity of sanctions and likelihood of being reported. Biological sex moderated the relationships between genetic relatedness and theft intentions, as well as between expectations of punishment and theft intentions. Specifically, when females expected higher severity of sanctions or likelihood of whistleblowing, they were less likely to report theft intentions, compared to males. The results of this study suggest that family business owners should protect against theft by all employees, including genetic relatives. Future research using field samples would help provide context for these findings. (C) 2017 Elsevier Ltd. All rights reserved.
13 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/010-210-309-412-58X tex.type: [object Object]
Keywords: Counterproductive behaviors; Evolutionary theory; Family business; Kinship; Lab experiment; Nepotism; Theft; dept.mgt; peer-reviewed

Making sense of mindfulness in management education - Yang, Charlie (Developing a Sustainability Mindset in Management Education, 2018)
Keywords: dept.mgt

Pay openness movement: Is it merited? Does it influence more desirable employee outcomes than pay secrecy? - Marasi, Shelly; Wall, Alison; Bennett, Rebecca J. (Organization Management Journal, 2018)
Organizations are currently moving toward increased pay openness in the workplace; thus, it is important to determine the influence pay communication practices (pay secrecy and pay openness) have on employee outcomes and whether the increase in pay openness is merited and more beneficial for organizations. The purpose of this article is to analyze pay communication’s influence on workplace deviance and organizational citizenship behaviors (OCBs). Specifically, pay secrecy practices are hypothesized to influence employees to engage in less OCBs and more workplace deviance. Informational justice and distributive justice perceptions are included as mediators. Pay secrecy leads to greater workplace deviance as well as less OCBs and justice perceptions and thus, inferring the pay openness movement is merited. A Pay Communication scale was developed and validated for this study. Practical implications, limitations, and future research directions are provided. © 2018 Eastern Academy of Management.
13 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/032-494-664-059-042, pop00257 tex.type: [object Object]
Keywords: dept.mgt; distributive justice; informational justice; organizational citizenship behaviors; pay communication; pay openness; pay secrecy; peer-reviewed; workplace deviance

A Study on Cloud Computing Adoption Within Small and Mid-Size Businesses (smbs) - Richardson, Anthony; Mate, Geoffrey (International Journal of Interdisciplinary Research, 2018)
A growing number of organizations have difficulty scaling-up their IT infrastructure to handle their growing needs and increased resource demands. Digital Technology Platforms (DTPs) have been identified by Gartner, Inc. as one of the top 10 strategic technology trends of 2017. While DTPs may be mainstream and easily adopted by large enterprise-sized organizations, there is an opportunity for such platforms within Small and Mid-Size Businesses (SMBs). The bottom line is that computing and server hardware is expensive for SMBs. Furthermore, it may be difficult for SMBs to assess and price the labor and resources needed for a company to have acceptable performance while controlling costs. The purpose of this paper is to examine how cloud computing technologies are adopted by SMBs and the respective drivers associated with costs and capability that may reduce costs for an organization. This paper explores how four variables – Robust Capability, Limited Capability, Cost Constraint, and Resource Abundance interact to impact the adoption of DTPs within SMBs. Adopters of DTPs are classified as Efficient, Proactive, Resistive, and Reactive. With respect to adoption efficacy, a model is proposed for assessing the capability and resource readiness as correlated to SMB adoption of DTPs. A study of 12 SMBs and the implementations of DTPs is presented and posited with the proposed adoption model. Due to the extensive investments required in procuring infrastructure services –adoption enablement is imperative for SMB-sized organizations to realize a return on investment. Implications are discussed.
Keywords: dept.bis; dept.mgt; peer-reviewed; ⛔ No DOI found

Bullying in the workplace: The great balancing act of victim rights and organizational policies - Wall, Alison E.; Smith, Robert A.; Nodoushani, Omid (Journal of Competitiveness Studies, 2018)
Bullying in the workplace is considered a growing epidemic and organizations are struggling to ensure appropriate responses and protocol as there is currently no individual statutory remedy. This paper provides a synthesis of current research regarding workplace bullying, legal policies, efforts to promote remedial legislation and organizational responsibility and outcomes. Workplace bullying is addressed from several perspectives including organizational consequences, characteristics of both victims and perpetrators, the current state of legislation and best practices for organizational policy. The paper also provides a discussion of developing issues related to increased technology and social media usage.
Keywords: BULLYING in the workplace; CYBERBULLYING; VICTIMS of bullying; VIOLENCE in the workplace; WORK environment; dept.mgt; peer-reviewed; ⛔ No DOI found

Business schools, brand innovation and archetypal tradeoffs - Page Jr, Robert A.; Falk, Louis K. (Quarterly Review of Business Disciplines, 2018)
Keywords: dept.mgt; peer-reviewed; ⛔ No DOI found

How do humans interact with chatbots?: an analysis of transcripts - Park, Mina; Aiken, Milam; Salvador, Laura (International Journal of Management and Information Technology, 2018)
14 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/137-012-207-389-604 tex.type: [object Object]
Keywords: dept.bis; dept.mgt; peer-reviewed

More than a decade later: Arational decision cycles in post-Hurricane Katrina disaster management - Smith Jr, Robert A.; Page Jr, Robert A.; Badr, Kauther S. (Quarterly Review of Business Disciplines, 2018)
Keywords: dept.mgt; peer-reviewed; ⛔ No DOI found

Personality testing by employers: Balancing the need for qualified workers with individual rights - Smith, Robert A.; Badr, Kauther S.; Wall, Alison E. (Competition forum, 2018)
Keywords: dept.mgt; peer-reviewed; ⛔ No DOI found

Corporate slavery: Does it still exist? - Wall, A.; Smith, R.; Nodoushani, O. (Competition Forum, 2018)
Keywords: dept.mgt; peer-reviewed; ⛔ No DOI found

Teaching international business as an opportunity to develop cultural sensitivity - Frank, Ellen J. (Journal of Teaching in International Business, 2017)
Business program graduates are expected to perform with cultural sensitivity in international and intercultural professional environments. In order to support student development of the necessary mindset, a variety of assignments and activities have been integrated into the undergraduate International Business (IB) course. This article describes several types of exercises that can be used by anyone teaching this course or one where cultural sensitivity is an important component. No quantitative data are presented, nor are any claims made to the efficacy of these assignments. But student comments point to increased cultural sensitivity and a better understanding of the issues of globalization. © 2017 Taylor & Francis Group, LLC.
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/118-584-012-132-547, pop00249 tex.type: [object Object]
Keywords: Cross-cultural awareness; Cultural sensitivity; Globalization; International business (IB); dept.mgt

Classical literature gives life to business paradox and systems integration - Page, Robert; Andoh, Samuel; Smith, Robert (Administrative Issues Journal Education Practice and Research, 2017)
1 citations (Crossref) [2023-10-31]
Keywords: dept.eco; dept.mgt

Workplace bullying: A growing epidemic - Wall, Alison E.; Smith, Robert A.; Nodoushani, Omid (Competition Forum, 2017)
Keywords: dept.mgt; peer-reviewed; ⛔ No DOI found

Strategic corporate giving - Cha, Wonsuk; Park, Miyoung (International Journal of Corporate Strategy and Social Responsibility, 2017)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/065-236-019-432-014
Keywords: dept.mgt

Leadership: A gateway to organizational innovation - Nodoushani, Omid; Stewart, Carol; Wall, Alison (Competition Forum, 2017)
Keywords: dept.mgt; peer-reviewed; ⛔ No DOI found

Fair treatment of unauthorized restaurant workers as a sustainable competitive advantage - Page Jr, Robert A.; Smith Jr, Robert A.; Shrestha, Smita (Quarterly Review of Business Disciplines, 2017)
Keywords: dept.mgt; peer-reviewed; ⛔ No DOI found

Entrepreneurship education: A look at two universities - Pauna, Diana; Frank, Ellen J. (Global Journal of Entrepreneurship, 2017)
Keywords: dept.mgt; ⛔ No DOI found

Insidious incentives: A critical exercise to explore knowing, context, and multiple views. - Stepanovich, Paul L; Hopkins, Pamela J; Stark, Ernest (Management Teaching Review, 2017)
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/023-329-460-828-676
Keywords: dept.mgt

Strategic conflict: A systems based pedagogical simulation - Stepanovich, Paul; Mueller, James (International Journal of Social Science and Education, 2017)
The paper describes a pedagogical simulation that allows students to explore strategic goal conflict within the context of systems theory. Systems theory emphasizes, among other things, complexity, non-linear relationships, unintended consequences, time delays, and dynamics. Another important aspect of systems thinking is contextual thinking, where objects or relationships cannot be taken as standalone or absolute, but are critically dependent on system structure and the environment. And while strategic planning has long emphasized the importance of environment, it may be difficult for students to experience or appreciate its importance in the planning process. The simulation provides an experiential exercise for a strategy course. The paper provides a summary of systems thinking and strategic goal conflict, a description of the simulation, teaching notes, and experience with the exercise.
Keywords: dept.mgt; ⛔ No DOI found